Interaction of novel hydrocolloids from indigenous New Zealand ferns with κ-carrageenan and low-acyl gellan gum - Felicia Zhi Wen Peh; Xu Yong Han; Kelvin K.T. Goh; Mark R. Waterland; Lara Matia-Merino (Food Hydrocolloids, 2027)

CATA-optimize-to-ideal (CATA-OI): A consumer-driven product optimization method compared with liking/disliking CATA and ideal profile method - Jisu Park; Jae-young Han; Seo-Jin Chung; Sara R. Jaeger; Eunkyoung Yoon; Sohyun Kim; Woobong Lee; Yangsoo Byeon (Food Research International, 2026)

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Decoding genetic basis of nitrogen use efficiency in maize using AI-generated deep phenotypes - Haoyan Yang; Lingju Zeng; Xiangjian Gou; Yang Shao; Xianlong Song; Shuang Zhang; Xiaoyan Qian; Zhenwei Zhang; Xiao Wang; Haitao Li; Bo Peng; Juliet Nkiruka Anyanwu; et al. (Molecular Plant, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

Behavioural thermoregulation segregates sick and healthy fish to enable selective treatment - Massiel F. Copara Chino; Jayoon Lee; Yujin Han; Julia G. Neyedly; Matthew L. Michnik; Patrick Whittaker; Kathryn Smith; Keith B. Tierney; Yamila Carpio; Mario P. Estrada; Mark D. Fast; Brian Dixon; et al. (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Retraction notice to “Enhancing battery pack safety against cone impact using machine learning techniques and Gaussian noise” [Process Saf. Environ. Prot. 191 (2024) 448–465] - Qian Zhang; Shaoyong Han; Azher M. Abed; Ali Basem; Mohamed R. El-Sharkawy; Bashir Salah; Ibrahim Mahariq (Process Safety and Environmental Protection, 2026)

Exploring the longitudinal links of chemosensory hedonic capacity with appetitive traits and satisfaction with food-related life in Chinese older adults - Jiayi Han; Yueyang Xiao; Peiyi Wang; Yunyi Cheng; Wesley R. Barnhart; Jinbo He (Food Quality and Preference, 2026)

Organosulfur compound-driven mobilization of colloidal metals and organic matter from acid mine drainage-contaminated paddy soils - Meihui Ren; Han Ye; Lijuan Zeng; Jingyang Li; Guining Lu; Fei Huang; John R. Reinfelder; Xiaoyun Yi; Chenyan Ma; Zhi Dang; Chuling Guo (Journal of Hazardous Materials, 2026)

How does the built environment affect obesity? A review from the perspective of urban planning - H. Wu; G. Han; L. Yang; R. Liang (International Journal of Environmental Science and Technology, 2026)

Impact of age and rurality on colorectal cancer outcomes in the United States - Caitlyn Grunert; Meng-Han Tsai; Charles R. Rogers; Sydney Howard; Rachel Hogg-Graham; Courtney Martin; Darwin Conwell; Adetunji T. Toriola; Avinash Bhakta; Justin X. Moore (Cancer Causes & Control, 2026)
Background While overall colorectal cancer (CRC) rates have declined in the United States (U.S.), early-onset CRC (EO-CRC), diagnosed before age 50, has increased. Rural U.S. residents face higher CRC incidence than non-rural counterparts. We aimed to examine the relationship between age at diagnosis and EO-CRC outcomes and whether rurality modify these associations. Methods We analyzed data from 835,907 patients aged 20–79 years in the 2006–2020 SEER Program. Rurality was defined using U.S. Department of Agriculture Rural–Urban Commuting Area (RUCA) codes. Multivariable logistic regression models were used to examine associations between age, rurality, and late-stage CRC diagnosis. Competing-risk regression models were applied to evaluate CRC-specific mortality, accounting for non–CRC deaths. Patients aged 50–59 years residing in non-rural areas served as the reference group for joint age–rurality analyses. All models adjusted for demographic, socioeconomic, clinical, and treatment factors. Results Patients aged 30–39 (aOR: 1.49, 95% CI: 1.44–1.54) and 40–49 (aOR: 1.43, 95% CI: 1.40–1.46) had significantly higher odds of late-stage CRC compared with those aged 50–59, with the strongest associations observed among non-rural patients aged 30–39 (aOR: 1.52, 95% CI: 1.46–1.58). In competing-risk models, rural patients were at higher CRC-specific mortality across all age groups, with relative hazard increases ranging from 8% in older adults (70-79) to 21% in younger adults (20-29) compared with their non-rural counterparts. Conclusion Adults aged 30–49 had higher odds of late-stage CRC than those 50–59, especially in non-rural areas. Rural residence was associated with higher CRC-specific mortality across all ages. Overall, age more strongly predicted late-stage diagnosis, while rurality more strongly predicted mortality. Earlier detection and improved clinical awareness in younger adults may reduce advanced-stage disease and CRC deaths.

Analysis of Helium Monte Carlo Data for the ISS-CREAM Instrument - A. Bagga; S. Aggarwal; Y. Amare; D. Angelaszek; D.P. Bowman; Y.C. Chen; G.H. Choi; M. Copley; L. Derome; Z.M. Dorris; L. Eraud; J.H. Han; et al. (Advances in Space Research, 2026)

3,3'-Dichlorobiphenyl (PCB 11) alters the hepatic expression of cytochrome P450 enzymes in the liver of mouse dams exposed orally during pregnancy and lactation - Crystal M. Roach; Nate R. Koester; Xueshu Li; Jeonghyeon Ahn; R. Marshall Pope; Rebecca J. Wilson; Rosalia Mendieta; Anthony Valenzuela; Weiguo Han; Xinxin Ding; Pamela J. Lein; Hans-Joachim Lehmler (Archives of Toxicology, 2026)
Healthy maternal metabolism is critical during pregnancy and lactation to support fetal development and protect against environmental toxins. Polychlorinated biphenyl 11 (PCB 11), a lower-chlorinated, non-legacy congener, is detected in human serum, including pregnant women and children; however, its impact during these sensitive life stages remains poorly understood. This study presents the first comprehensive hepatic proteome analysis of mouse dams exposed to PCB 11 during pregnancy and lactation. Female C57BL/6 J mice received daily oral doses of PCB 11 (0, 1.0 or 6.0 mg/kg) prior to conception through lactation. At postpartum day 21, brain, liver, and serum samples were analyzed for PCB 11 and its metabolites, and hepatic proteomic changes were assessed. Low detection of PCB 11 and its metabolites was observed in tissues, suggesting rapid clearance. Metabolite screening revealed OH-PCB 11, PCB 11 sulfate, and OH-PCB 11 sulfate metabolites in serum. Global proteomics identified significant alterations in hepatic protein expression, including downregulation of cytochrome P450 enzymes, solute carriers, and enzymes involved in fatty acid and steroid metabolism. Pathway enrichment analyses indicated disruptions in xenobiotic metabolism and endocrine pathways. These findings suggest that PCB 11 exposure during pregnancy and lactation impairs hepatic detoxification and metabolic capacity, potentially compromising maternal and offspring health. This work highlights the need for further investigation into the long-term consequences of PCB 11 exposure during pregnancy and lactation.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Quantifying volcanism during Oceanic Anoxic Event 2 constrained by sedimentary mercury - Yi Zhang; Hanwei Yao; Yinggang Zhang; Paul R. Bown; Stephen E. Grasby; Runsheng Yin; Kaibo Han; Huifang Guo; Chengshan Wang; Xi Chen (Global and Planetary Change, 2026)

Dissection of Fusarium head blight resistance in a modified nested association mapping panel of synthetic and bread wheat germplasm - Anil Karmacharya; Dhondup Lhamo; Krishna Acharya; Qijun Zhang; Han-Chang Chang; Shaobin Zhong; Andrew J. Green; Jason D. Fiedler; Mingcheng Luo; Kirk M. Anderson; Amanda R. Peters Haugrud; Elias M. Elias; et al. (Theoretical and Applied Genetics, 2026)

Enantioselective interactions of silver nanoparticles and chiral antibiotics in driving resistance evolution in activated sludge - Fang Zhao; Zhao Yang; Yifan Xiao; Ganghua Han; Kim R. Hardie; Mark Bartlam; Yingying Wang (Water Research, 2026)

Highly virulent Aerococcus viridans activates the RIPK3 signaling pathway, inducing necroptosis and inflammation in bovine mammary epithelial cells and murine mammary tissue - Siyu Meng; Maolin Xu; Xian Deng; Zimeng Zhu; Herman W. Barkema; John P. Kastelic; Eduardo R. Cobo; Bo Han; Gang Liu (Veterinary Microbiology, 2026)

The analysis of road stormwater runoff pollution in the typical coastal city of Lianyungang, East China - H. Leng; H. Luo; R. Han; W. Wu; B. Song; Y. Zhao; B.-J. He (International Journal of Environmental Science and Technology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

DDT exposure induces microglial activation and disease-associated microglial signatures: Relevance to mechanisms of Alzheimer’s disease - Isha Mhatre-Winters; Aseel Eid; Nicole Blum; Yoonhee Han; Ferass M. Sammoura; Long-Jun Wu; Jason R. Richardson (NeuroToxicology, 2025)

A full sub-2 nm and acid-resistant MOF-COF ionic diode membrane for efficient ionic gradient power generation - Norman C.-R. Chen; Po-Chun Han; Li-Hsien Yeh; Yu-Hsiang Peng; Chia-An Lung; Yusuke Yamauchi; Kevin C.-W. Wu (Chemical Engineering Journal, 2025)

Hofmeister-regulated fabrication of piezoelectric β-PVDF membrane: The specific ion effect on the membrane formation, piezoelectric property, and anti-fouling performance - R.D. Hope T. Cayron; Hannah Faye M. Austria; Tsung-Han Huang; Gabriel V. Carballo; Smrutiranjan Nayak; Alvin R. Caparanga; Wei-Song Hung; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

The effect of light, aeration and temperature on the growth and phenolic content of cultivated Ecklonia cava gametophytes (Phaeophyceae) and their antioxidant properties - Ilias Semmouri; Hojun Lee; Samira Alahyaribeik; Juan Miguel Baldominos Botas; Phara Claeys; Taejun Han; Colin R. Janssen; Mahta Mirzaei; Jana Asselman; Jihae Park (Journal of Applied Phycology, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Development of a High-throughput Morphological Assay for Evaluating Mesenchymal Stromal Cell-derived Extracellular Vesicle Modulation of Brain Pericyte Secretory Phenotype - Courtney E. Campagna; Andrew M. Larey; Kanupriya R. Daga; Morgan Roos; Sneha Ghosh; Neil Grimsey; Jin Han; Ross A. Marklein (Stem Cell Reviews and Reports, 2025)
Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) are a promising therapeutic tool for treating many neurodegenerative diseases. Neuroinflammation plays a major role in many of these conditions through an orchestration of interdependent processes that lead to the breakdown of the blood-brain barrier (BBB), infiltration of immune cells and neuronal death. MSC-EVs have shown preliminary evidence of modulating neuroinflammation, but their mechanisms of action are still unknown. Therefore, we explored the potential of MSC-EVs in modulating brain pericytes, a cell type that plays a critical role in BBB maintenance but has not been investigated as a therapeutic target for MSC-EVs. Brain pericytes are multifaceted cells that can modulate neuroinflammation through their involvement in BBB homeostasis, as well as the innate and adaptive immune response. Pericyte morphology has been shown to change in response to inflammatory stimuli in vivo, hence, we used this behavior to develop a quantitative morphological profiling approach to assess the immunomodulatory function of MSC-EVs in a high-throughput, low-cost manner. Using this assay, we were able to demonstrate that MSC-EVs manufactured under various conditions (2D, 3D, and in response to cytokine priming) could induce distinct pericyte morphological responses indicative of changes in secretion of chemokines and cytokines relevant to neuroinflammation.

Nannoplankton response indicates intra-OAE2 cooling (Plenus Cold Event) in southeastern Tethys (Qiangdong, Tibet) - Yi Zhang; Hanwei Yao; Paul R. Bown; Huifang Guo; Kaibo Han; Cinzia Bottini; Chengshan Wang; Xi Chen (Global and Planetary Change, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Imaging viscosity after the 2021 Mw 7.4 Maduo earthquake: Insights on the regional rheology variation beneath the Bayan Har block - Zhen Li; Wei Xiong; Andrew Hooper; Zeyan Zhao; Yuan Gao; John R. Elliott; Tim J. Wright; Han Yue; Teng Wang (Earth and Planetary Science Letters, 2025)

Seismic observations from injection experiments and a recharge event in a karst aquifer: potential compressed air pocket release - Andrew J. Luhmann; Susan L. Bilek; Matthew D. Covington; Ronni Grapenthin; Han Byul Woo; Jacob Alexander Gochenour; E. Calvin Alexander; Scott C. Alexander; Martin R. Larsen (Hydrogeology Journal, 2025)
After deploying a seismic network above a karst aquifer that feeds Bear Spring in Minnesota, USA, three injection experiments were conducted, which involved pouring ~10,000 L of water just above an overflow spring to induce and characterize ambient seismic noise from subsurface water flow. A rainstorm event followed the second experiment and caused the overflow spring to start flowing with meters of water level rise, increasing the total spring discharge (perennial and overflow emanations) from ~100 to 300 L/s. Water level, electrical conductivity, and temperature data were used to estimate the conduit hydraulic diameter of ~0.06 m from the second injection experiment and ~0.5 m from the recharge event, which suggested both open channel and full pipe conduit flow. The rainstorm led to the largest seismic signals over a 5 s period while water levels rose, producing ground motion up to ~0.5 mm/s, possible oscillatory behavior, and 1–150 J of radiated seismic energy at frequencies of ~30–50 and 70–90 Hz (similar to signal frequencies when the large water slug from the second injection experiment reached a sump or water-filled passage). The seismic sources originated from multiple directions. The calculations suggest these signals came from conduits with air pockets that were compressed from rising water levels and later released via ventilation pathways. Seismic records of this process enable identification of the change in mode of water level propagation and potential delineation of unknown subsurface pathways, facilitating karst aquifer characterization beyond what is possible with traditional monitoring strategies.

Corrigendum to “Questionnaire-assessed atypical sensory sensitivity is prospectively related to higher ARFID psychopathology, higher food neophobia, and lower satisfaction with food-related life in an online sample of Chinese older adults” [Food Quality and Preference 122 (2025) 105303] - Yueyang Xiao; Jiayi Han; Hana F. Zickgraf; Wesley R. Barnhart; Yiqing Zhao; Jinbo He (Food Quality and Preference, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

uPAR-targeted senolytic delivery to enhance cancer therapy - Thi Oanh Oanh Nguyen; Bao Loc Nguyen; Basavaraj R. Patil; Ngoc Duy Le; Beomsu Kim; Sung Giu Jin; Han-Gon Choi; Sae Kwang Ku; Huy Xuan Luong; Jeonghwan Kim; So-Young Park; Jong Oh Kim (Journal of Pharmaceutical Investigation, 2025)

Phenotypic Trait Monitoring of Victoria amazonica Plants Using Unmanned Aerial Vehicles - Anjali Rai; Pranav R. T. Peddinti; Byungmin Kim; Sung Soo Han; Seon Joo Park (Journal of the Indian Society of Remote Sensing, 2025)

Unraveling the drivers of forage quality variation in the Serengeti - Yuhong Li; Sanne Piek; Emilian P. Mayemba; Kelvin R. Shoo; Michiel P. Veldhuis; Han Olff (Ecology, 2025)
Variation in forage quality is a key dimension of herbivore resource partitioning, but the main determinants of such variation across environmental gradients remain poorly understood. It is especially unclear how much variation in plant nutrient contents and stoichiometry is driven by plant species turnover versus by intraspecific variation across sites. We investigated variation in forage quality across nine sites along a key environmental gradient of increasing rainfall and decreasing soil fertility in the Serengeti National Park, Tanzania. We compared leaf elemental contents of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sodium (Na) and three nutrient ratios (N:P, Ca:P, and K:Na) between sites, between species within the same site, and between sites within the same species. Site‐average N, P, and K leaf contents decreased with increasing rainfall and decreasing soil fertility. The decline in N and K was primarily associated with species turnover, with their contents remaining relatively stable within species. The decline in P was associated with a combination of species turnover and intraspecific variation, with intraspecific P content decreasing strongly with increasing rainfall (decreasing soil fertility) across sites. Variation in site‐average Ca, Mg, and Na leaf contents did not significantly correlate with rainfall or soil fertility and was mainly explained by species turnover between sites. Comparing leaf nutrient content and ratios to literature‐derived nutritional requirements for large herbivores suggests that Na is severely limiting in this ecosystem. K seems sufficient everywhere, and the other elements are moderately limiting. If Serengeti herbivores rely on plants for their nutrient intake and are nutrient‐limited, these results suggest herbivores with high N, Ca, or Mg requirements should optimize their diet by selecting particular species, relatively independent of sites. Herbivores with a high P requirement can instead best select particular sites, relatively independent of plant species. To obtain sufficient Na, herbivores can target particular species at particular sites. Thus, resource partitioning among Serengeti herbivores may occur at different levels for different elements. Interspecific variation in herbivore nutrient requirements would then drive resource partitioning both across sites (for P and Na) and between plant species (N, Ca, Mg, and Na).

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Oxidized lignite reduces greenhouse gas emissions, nitrogen loss, and heavy metal bioavailability in pig manure - Jing Hu; Clayton R. Butterly; Bing Han; Wei Zhang; Ji-Zheng He; Deli Chen (Journal of Environmental Chemical Engineering, 2025)

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Selective and sensitive Electrocatalytic behavior of hierarchical SnS decorated on La2Sn2O7 embedded carbon nanofibers for detection of antioxidant diphenylamine in fruits samples - Gagankumar Sakleshpur Kumar; Harshitha B. Tyagaraj; Ali Mohammadi; Shalmali R. Burse; Hyun Uk Lee; Kugalur Shanmugam Ranjith; Yun Suk Huh; Young-Kyu Han (Food Chemistry, 2025)

Green manuring combined with optimal water management achieves a triple-win for paddy soil quality, rice productivity, and environmental benefits - Guopeng Zhou; Zhengbo Ma; Shang Han; Danna Chang; Jinxin Sun; Han Liu; Guodong Zhou; Qingxu Ma; Jia Liu; Ji Wu; David R. Chadwick; Davey L. Jones; et al. (Agriculture, Ecosystems & Environment, 2025)

Zoning effects on fish populations in a key Chinese multi-use marine protected area - Xu Zeng; Yue Liu; Shouyu Zhang; Cong Zeng; Dongyan Han; Kisei R. Tanaka; Mackenzie D. Mazur; Ling Cao (Ocean & Coastal Management, 2025)

Complexity in long-term stand dynamics of mixed-species, multi-cohort stands using an imputation/copula tree growth model - Yung-Han Hsu; John A. Kershaw; Aaron R. Weiskittel; Mark J. Ducey (Forest Ecology and Management, 2025)

Environmental Gradients Linked to Human Impacts, Not Species Richness, Drive Regional Variation in Community Stability in Coral Reef Fishes - Cheng‐Han Tsai; Sean R. Connolly (Ecology Letters, 2025)
The stabilising effect of biodiversity on aggregate community properties is well‐established experimentally, but its importance in naturally assembled communities at larger scales requires considering its covariation with other biotic and abiotic factors. Here, we examine the diversity–stability relationship in a 27‐year coral reef fish time series at 39 reefs spanning 10° latitude on Australia's Great Barrier Reef. We find that an apparent relationship between species richness and synchrony of population fluctuations is driven by these two variables' covariation with proximity to coastal influences. Additionally, coral cover volatility destabilises fish assemblages by increasing average population variability but not synchrony, an effect mediated by changes in the intensity of density regulation in the fish community. Our findings indicate that these two environmental factors, both of which are strongly influenced by anthropogenic activity, impact community stability more than diversity does, but by distinct pathways reflecting different underlying community‐dynamic processes.

Rodent Diets Incorporated with Live Biotherapeutic Products (LBPs): An Innovative Dosing Strategy to Support Preclinical Animal Studies on LBP Intervention - Haixi Cui; Yongrong Zhang; Hua Yu; R. Gary Hollenbeck; Lydia Nyasae; Yihan Wang; Yiguang Han; Zhiyong Yang; Hanping Feng; Stephen W. Hoag (AAPS PharmSciTech, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Efficient removal of cationic malachite green using co-pyrolyzed corn straw biochar-montmorillonite composites - Xiaodong Yang; Zhiyong Hou; Xuefei Yang; Minghui Li; Yuanxia Guo; Kai Wang; Shuaiqi Luo; Jin Zhao; Pengkai Sun; Qiang Yang; Rui Chen; Yan Yan; et al. (Journal of Environmental Management, 2025)

Heavy metal retention mechanism in geopolymer-based flocculation-solidification of waste engineering spoil: Migration characteristic and sodium dodecyl sulfate enhancement - Xiaohui Sun; Zhihao Han; Xiangsheng Chen; Minghui Liu; Chenyu Wang; Zijun Dong; Silin Wu; Zhongping Chen; Mostafa R. Abukhadra (Journal of Environmental Chemical Engineering, 2025)

Excitation functions for fast neutron induced reactions on Al, Zr, In and Au - B. Liu; G. Tian; R. Han; F. Shi; H. Sun; Z. Chen; Z. Zhang; Q. Li; P. Luo (Annals of Nuclear Energy, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Questionnaire-assessed atypical sensory sensitivity is prospectively related to higher ARFID psychopathology, higher food neophobia, and lower satisfaction with food-related life in an online sample of Chinese older adults - Yueyang Xiao; Jiayi Han; Hana F. Zickgraf; Wesley R. Barnhart; Yiqing Zhao; Jinbo He (Food Quality and Preference, 2025)

Nutrient effects on plant diversity loss arise from nutrient identity and decreasing niche dimension - Yang Peng; Jianxia Yang; Eric W. Seabloom; Andrew R. Leitch; Ilia J. Leitch; Ruzhen Wang; Cunzheng Wei; Xingguo Han (Ecology, 2025)
Two hypotheses have been used to explain the loss of plant diversity with nutrient addition. The nutrient identity hypothesis posits that biodiversity loss is due to a specific limiting nutrient, such as nitrogen (N) or phosphorus (P), while the niche dimension hypothesis posits that adding a larger number of limiting nutrients, regardless of their identity, results in biodiversity loss. These two hypotheses have not previously been tested together simultaneously. Here, we conduct that analysis to enable their relative effect sizes to be compared. We manipulated the supply of eight nutrients in the same experimental meadow grassland site to isolate the effects of the identity of added nutrients versus the number of added nutrients on biodiversity loss. We found support for both hypotheses, with the largest negative effects on biodiversity measures being due to N, or N and P treatment, with additional more minor effects of the number of added nutrients. Structural equation models (SEMs) suggested both identity and number of added nutrients had direct negative effects on biodiversity, likely caused by species' innate ability to competitively respond to nutrients, especially in response to disease, herbivory, and stress. SEMs also suggested indirect effects arising from nutrient‐driven increases in aboveground biomass, which resulted in intensified competition for light and the competitive exclusion of short‐statured species. These effects were exacerbated by the nutrients N and P which caused a shift in biomass accumulation from belowground to aboveground. The results highlight that a multi‐nutrient perspective will improve our ability to effectively manage, monitor, and restore ecosystems.

Efficient removal of aqueous ciprofloxacin antibiotic by ZnO/CuO-bentonite composites synthesized via carbon-bed pyrolysis of bentonite and metal co-precipitation - Xiaodong Yang; Xuefei Yang; Zhiyong Hou; Minghui Li; Shuaiqi Luo; Jin Zhao; Kai Wang; Yuanxia Guo; Pengkai Sun; Fang Tan; Yan Yan; Lulu Liu; et al. (Science of The Total Environment, 2024)

Reconstructing Tibetan Plateau lake bathymetry using ICESat-2 photon-counting laser altimetry - Xiaoran Han; Guoqing Zhang; Jida Wang; Kuo-Hsin Tseng; Jiaqi Li; R. Iestyn Woolway; C.K. Shum; Fenglin Xu (Remote Sensing of Environment, 2024)

RETRACTED: Enhancing battery pack safety against cone impact using machine learning techniques and Gaussian noise - Qian Zhang; Shaoyong Han; Azher M. Abed; Ali Basem; Mohamed R. El-Sharkawy; Bashir Salah; Ibrahim Mahariq (Process Safety and Environmental Protection, 2024)

Fabrication of zein/modified cyclodextrin nanofibers for the stability enhancement and delivery of curcumin - Yao Hu; Nicholas H. Rees; Chao Qiu; Jinpeng Wang; Zhengyu Jin; Ran Wang; Yinhua Zhu; Han Chen; Pengjie Wang; Siyuan Liu; Fazheng Ren; Gareth R. Williams (Food Hydrocolloids, 2024)

Uncovering mediational pathways behind racial and socioeconomic disparities in brain volumes: insights from the UK Biobank study - May A. Beydoun; Hind A. Beydoun; Marie T. Fanelli-Kuczmarski; Yi-Han Hu; Danielle Shaked; Jordan Weiss; Shari R. Waldstein; Lenore J. Launer; Michele K. Evans; Alan B. Zonderman (GeroScience, 2024)
Mediation pathways explaining racial/ethnic and socioeconomic (SES) disparities in structural MRI markers of brain health remain underexplored. We examined racial/ethnic and SES disparities in sMRI markers and tested total, direct, and indirect effects through lifestyle, health-related, and cognition factors using a structural equations modeling approach among 36,184 UK Biobank participants aged 40–70 years at baseline assessment (47% men). Race (non-White vs. White) and lower SES-predicted poorer brain sMRI volumetric outcomes at follow-up, with racial/ethnic disparities in sMRI outcomes involving multiple pathways and SES playing a central role in those pathways. Mediational patterns differed across outcomes, with the SES-sMRI total effect being partially mediated for all outcomes. Over 20% of the total effect (TE) of race/ethnicity on WMH was explained by the indirect effect (IE), by a combination of different pathways going through SES, lifestyle, health-related, and cognition factors. This is in contrast to < 10% for total brain, gray matter (GM), white matter (WM), and frontal GM left/right. Another significant finding is that around 57% of the total effect for SES and the normalized white matter hyperintensity (WMH) was attributed to an indirect effect. This effect encompasses many pathways that involve lifestyle, health-related, and cognitive aspects. Aside from WMH, the percent of TE of SES mediated through various pathways ranged from ~ 5% for WM to > 15% up to 36% for most of the remaining sMRI outcomes, which are composed mainly of GM phenotypes. Race and SES were important determinants of brain volumetric outcomes, with partial mediation of racial/ethnic disparities through SES, lifestyle, health-related, and cognition factors.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Inclusion of oil from transgenic Camelina sativa in feed effectively supplies EPA and DHA to Atlantic salmon (Salmo salar) grown to market size in seawater pens - Douglas R. Tocher; Matthew Sprague; Lihua Han; Olga Sayanova; Fernando Norambuena; Johnathan A. Napier; Mónica B. Betancor (Food Chemistry, 2024)

Effect of solid-state fermentation on the functionality, digestibility, and volatile profiles of pulse protein isolates - Andrea K. Stone; Dai Shi; Enyu Liu; Zahra Jafarian; Caishuang Xu; Aarti Bhagwat; Yuping Lu; Leonid Akhov; Jessica Gerein; Xiumei Han; L. Irina Zaharia; Nandhakishore Rajagopalan; et al. (Food Bioscience, 2024)

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Spatial planning offshore wind energy farms in California for mediating fisheries and wildlife conservation impacts - Crow White; Yi-Hi Wang; Ryan K. Walter; Benjamin I. Ruttenberg; Danny Han; Eli Newman; Ethan R. Deyle; Sucharita Gopal; Les Kaufman (Environmental Development, 2024)

Enhancing predictive understanding and accuracy in geological carbon dioxide storage monitoring: Simulation and history matching of tracer transport dynamics - Sabber Khandoozi; Weon Shik Han; Kue-Young Kim; Zhenxue Dai; Mohamed Mehana; David R. Cole; Mohamad Reza Soltanian (Chemical Engineering Journal, 2024)

Tachol1 QTL on mouse chromosome 1 is responsible for hypercholesterolemia and diet-induced obesity - Jung Han Kim; Marvin A. Simpkins; Nicholas T. Williams; Emma Cimino; Jadyn Simon; Tanner R. Richmond; Jared Youther; Hannah Slutz; James Denvir (Mammalian Genome, 2024)

Leveraging meta-regression to test if medication effects on cue-induced craving are associated with clinical efficacy - Steven J. Nieto; Han Du; Lindsay R. Meredith; Suzanna Donato; Molly Magill; Lara A. Ray (Psychopharmacology, 2024)
Rationale The alcohol cue exposure paradigm is a common method for evaluating new treatments for alcohol use disorder (AUD); however, it is unclear if medication-related reductions in cue-induced craving in the human laboratory can predict the clinical success of those medications in reducing alcohol consumption during clinical trials. Objectives To use a novel meta-analytic approach to test whether medication effect sizes on cue-induced alcohol craving are associated with clinical efficacy in clinical trials. Method We searched the literature for medications tested for AUD treatment using both the alcohol cue-reactivity paradigm and randomized clinical trials (RCTs). For alcohol cue-reactivity studies, we computed medication effect sizes for cue-induced alcohol craving (k = 36 studies, 15 medications). For RCTs, we calculated medication effect sizes for heavy drinking and abstinence (k = 139 studies, 19 medications). Using medication as the unit of analysis, we applied the Williamson-York bivariate weighted least squares estimation to account for errors in both independent and dependent variables. We also conducted leave-one-out cross validation simulations to examine the predictive utility of cue-craving medication effect sizes on RCT heavy drinking and abstinence endpoints. Results There was no significant relationship between medication effects on cue-induced alcohol craving in the human laboratory and medication effects on heavy drinking ( $$\widehat{β }$$ β ^ = 0.253, SE = 0.189, p = 0.090) and abstinence ( $$\widehat{β }$$ β ^ = 0.829, SE = 0.747, p = 0.133) in RCTs. Conclusions The preliminary results of the current study challenge the assumption that alcohol cue-reactivity alone can be used as an early efficacy indicator for AUD pharmacotherapy development. These findings suggest that a wider range of early efficacy indicators and experimental paradigms be considered for Phase II testing of novel compounds.

IC100, a humanized therapeutic monoclonal anti-ASC antibody alleviates oxygen-induced retinopathy in mice - Huijun Yuan; Shaoyi Chen; Matthew R. Duncan; Juan Pablo de Rivero Vaccari; Robert W. Keane; W. Dalton Dietrich; Tsung-Han Chou; Merline Benny; Augusto F. Schmidt; Karen Young; Kevin K. Park; Vittorio Porciatti; et al. (Angiogenesis, 2024)
Background Retinopathy of prematurity (ROP), which often presents with bronchopulmonary dysplasia (BPD), is among the most common morbidities affecting extremely premature infants and is a leading cause of severe vision impairment in children worldwide. Activations of the inflammasome cascade and microglia have been implicated in playing a role in the development of both ROP and BPD. Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) is pivotal in inflammasome assembly. Utilizing mouse models of both oxygen-induced retinopathy (OIR) and BPD, this study was designed to test the hypothesis that hyperoxia induces ASC speck formation, which leads to microglial activation and retinopathy, and that inhibition of ASC speck formation by a humanized monoclonal antibody, IC100, directed against ASC, will ameliorate microglial activation and abnormal retinal vascular formation. Methods We first tested ASC speck formation in the retina of ASC-citrine reporter mice expressing ASC fusion protein with a C-terminal citrine (fluorescent GFP isoform) using a BPD model that causes both lung and eye injury by exposing newborn mice to room air (RA) or 85% O 2 from postnatal day (P) 1 to P14. The retinas were dissected on P14 and retinal flat mounts were used to detect vascular endothelium with AF-594-conjugated isolectin B4 (IB4) and citrine-tagged ASC specks. To assess the effects of IC100 on an OIR model, newborn ASC citrine reporter mice and wildtype mice (C57BL/6 J) were exposed to RA from P1 to P6, then 75% O 2 from P7 to P11, and then to RA from P12 to P18. At P12 mice were randomized to the following groups: RA with placebo PBS (RA-PBS), O 2 with PBS (O 2 -PBS), O 2 + IC100 intravitreal injection (O 2 -IC100-IVT), and O 2 + IC100 intraperitoneal injection (O 2 -IC100-IP). Retinal vascularization was evaluated by flat mount staining with IB4. Microglial activation was detected by immunofluorescence staining for allograft inflammatory factor 1 (AIF-1) and CD206. Retinal structure was analyzed on H&E-stained sections, and function was analyzed by pattern electroretinography (PERG). RNA-sequencing (RNA-seq) of the retinas was performed to determine the transcriptional effects of IC100 treatment in OIR. Results ASC specks were significantly increased in the retinas by hyperoxia exposure and colocalized with the abnormal vasculature in both BPD and OIR models, and this was associated with increased microglial activation. Treatment with IC100-IVT or IC100-IP significantly reduced vaso-obliteration and intravitreal neovascularization. IC100-IVT treatment also reduced retinal microglial activation, restored retinal structure, and improved retinal function. RNA-seq showed that IC100 treatment corrected the induction of genes associated with angiogenesis, leukocyte migration, and VEGF signaling caused by O 2 . IC100 also corrected the suppression of genes associated with cell junction assembly, neuron projection, and neuron recognition caused by O 2 . Conclusion These data demonstrate the crucial role of ASC in the pathogenesis of OIR and the efficacy of a humanized therapeutic anti-ASC antibody in treating OIR mice. Thus, this anti-ASC antibody may potentially be considered in diseases associated with oxygen stresses and retinopathy, such as ROP.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Oxygen supersaturation adds resistance to a cnidarian: Symbiodiniaceae holobiont under moderate warming in experimental settings - Silvia Arossa; Shannon G. Klein; Elisa Garuglieri; Alexandra Steckbauer; Anieka J. Parry; Jacqueline V. Alva Garcia; Taiba Alamoudi; Xinyuan Yang; Shiou-Han Hung; Octavio R. Salazar; Ramona Marasco; Marco Fusi; et al. (Frontiers in Marine Science, 2024)
Ocean warming reduces O 2 solubility and increases organismal O 2 demand, endangering marine life. Coastal ecosystems, however, experience O 2 supersaturation during peak daytime temperatures due to metabolic cycles. Recent discoveries show that this environmental supersaturation can reduce the vulnerability of tropical species to warming by satisfying their oxygen requirements. To test whether this also occurs within the cnidarian holobiont, we elevated internal O 2 in Cassiopea andromeda at nighttime (i.e. holobiont respiration prevails on Symbiodniaceae O 2 production) relying on bell pulsation for ventilation, then experimentally subjected them to thermal stress (+1°C day -1 ). Though ecologically unrealistic, this approach verified our hypothesis and eliminated confounding factors. Holobionts were exposed to either constant levels of 100% air saturation (100AS) or nighttime supersaturation (NSS; where 100% air saturation transitioned to O 2 supersaturation at nighttime). At sublethal temperatures, supersaturation mitigated reductions in holobiont size of ~ 10.37% (-33.418% ± 0.345 under 100AS vs -23.039% ± 0.687 under NSS). Supersaturation alleviated chlorophyll- a loss by 42.73% until 34°C, when counteraction of this process could not be sustained due to excessive thermal stress. Supersaturation also enriched potentially beneficial bacterial taxa of the microbiome and selected a more consistent bacterial community. Although modest, the detected effects show that a O 2 surplus increased the resistance of the holobionts to thermal stress.

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

Dual-functional Au-porous anodic alumina (PAA) sensors for enrichment and label-free detection of airborne virus with surface-enhanced Raman scattering - Jin Han; Xinlian Zhang; Robin R. Jones; Guodong Sui; Ventsislav K. Valev; Liwu Zhang (Building and Environment, 2024)

Bioturbation by Benthic Stingrays Alters the Biogeomorphology of Tidal Flats - Janne Nauta; Guido Leurs; Brian O. Nieuwenhuis; Donné R. A. H. Mathijssen; Han Olff; Tjeerd J. Bouma; Daphne van der Wal; Nadia Hijner; Aissa Regalla; Samuel Ledo Pontes; Laura L. Govers (Ecosystems, 2024)
Fishing-down-marine-food-webs has resulted in alarming declines of various species worldwide. Benthic rays are one examples of such overexploited species. On tidal flats, these rays are highly abundant and play an ecologically important role. They use tidal flats as refuge, feeding and resting grounds, during which they bury into the sediment, which results in sediment bioturbation. Changes in bioturbation intensity, following ray removal, may affect the biogeomorphology of tidal flats with possible cascading effects on the macrozoobenthic community. However, it is poorly understood how these indirect effects could influence ecosystem function. We therefore studied the geomorphic impact of benthic rays (specifically the pearl whipray/stingray Fontitrygon margaritella ) on the tropical tidal flats of the Bijagós Archipelago, Guinea-Bissau, on a landscape scale. We investigated 1) bioturbation rates by rays using drone and ground surveys, 2) the spatial distribution of ray pits on multiple tidal flats, 3) the impact of rays on sediment properties and macrozoobenthos by experimental exclusion (15 months). Benthic rays bioturbated 3.7 ± 0.35% of the tidal flat’s sediment surface per day over one single 24-h period, which equals a complete top-sediment-surface turnover every 27 days. The spatial distribution of ray pits was affected by tidal flat geomorphology since pits decayed faster at areas exposed to strong hydrodynamic forces. Predator exclusion altered sediment properties, leading to changes in sedimentation (− 17%) and erosion (− 43%) rates. In addition, macrozoobenthic species composition changed, marked by an increase in Capitellidae worms and a greater biomass of Malacostraca over time. These changes indicated substantial effects of ray bioturbation on the biotic and geomorphic landscape of tidal flats. Overall, we conclude that changing abundances of benthic rays can have clear landscape-wide geomorphological effects on intertidal ecosystems. These indirect consequences of fisheries should be incorporated in integrative management plans to preserve tidal flats and connected ecosystems.

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Spontaneous rupture of the right aortic sinus resulting in a sterile aorto-atrial fistula in a pet rabbit (Oryctolagus cuniculus) - L. Cheung; B.A. Scansen; R. Baden; C.Q. Sloan; M. Garcia; S. Han; M.J. Sadar (Journal of Veterinary Cardiology, 2024)

Corrigendum to “Characterization and functional properties of pH- and heated time-induced aggregates from red lentil protein” [Food Structure 37 (2023) 100342] - Han Du; Yichen Lin; Catherine Stanton; Davor Daniloski; Emanuele Zannini; R. Paul Ross; Song Miao (Food Structure, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

Hazard and risk characterization of 56 structurally diverse PFAS using a targeted battery of broad coverage assays using six human cell types - Lucie C. Ford; Hsing-Chieh Lin; Han-Hsuan D. Tsai; Yi-Hui Zhou; Fred A. Wright; Alexander Sedykh; Ruchir R. Shah; Weihsueh A. Chiu; Ivan Rusyn (Toxicology, 2024)

Catalytic oxidation of lignite by Pt/TiO2 can enhance cadmium adsorption capacity - Jing Hu; Bing Han; Clayton R. Butterly; Wei Zhang; Ji-Zheng He; Deli Chen (Journal of Hazardous Materials, 2024)

Room-temperature fabrication of garnet-type solid-electrolyte: Optimizing particle size for high ionic conductivity - Jinhyup Han; Anh Vu; Jae Jin Kim; Jihyeon Gim; Jason R. Croy; Tae H. Lee; Eungje Lee (Chemical Engineering Journal, 2024)

An analysis of lncRNAs related to fiber quality and the discovery of their target genes in a Gossypium hirsutum line with Gossypium mustelinum introgression - Baohua Wang; Meijun Ji; Hui Fang; Haijing Gu; Teame Gereziher Mehari; Jinlei Han; Wenxiang Feng; Xuehan Huo; Jingxia Zhang; Yu Chen; Jun Zhang; Allah Ditta; et al. (Theoretical and Applied Genetics, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

The impact of inter- and intra-species spore density on germination of the food spoilage fungus Aspergillus niger - Maryam Ijadpanahsaravi; L. Basten Snoek; Wieke R. Teertstra; Han A.B. Wösten (International Journal of Food Microbiology, 2024)

Semiconductor nanosheets for electrocatalytic self-coupling of benzaldehyde to hydrobenzoin - Li Gong; Chao Yue Zhang; Xiao Mu; Xu Han; Junshan Li; Jordi Arbiol; Jin Yuan Zhou; Tanja Kallio; Paulina R. Martínez-Alanis; Andreu Cabot (Chemical Engineering Journal, 2024)

The Role of the Cerebellum in Learning to Predict Reward: Evidence from Cerebellar Ataxia - Jonathan Nicholas; Christian Amlang; Chi-Ying R. Lin; Leila Montaser-Kouhsari; Natasha Desai; Ming-Kai Pan; Sheng-Han Kuo; Daphna Shohamy (The Cerebellum, 2023)

An investigation of the performance of polyamide membrane for the concentration of pomegranate and effect on the physical and sports health of patients with physical weakness: A novel study - Lei Han; R. Mohammadi; Hao Lei; M.H. Jazbizadeh; D. Semiromi (Food Bioscience, 2023)

Sensorimotor Cough Dysfunction in Cerebellar Ataxias - Emilie R. Lowell; James C. Borders; Sarah E. Perry; Avery E. Dakin; Jordanna S. Sevitz; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2023)

Assess the formation of disinfection by-products from pyrogenic dissolved organic matter (pyDOM): impact of wildfire on the water quality of forest watershed - Zhao Li; Pamela Rose V. Samonte; Han Cao; Jessica R. Miesel; Wenqing Xu (Science of The Total Environment, 2023)

Natural restoration exhibits better soil bacterial network complexity and stability than artificial restoration on the Loess Plateau, China - Xing Wang; Zhengchen Wang; Zhenjiao Zhang; Yang Yang; Carolyn R. Cornell; Weichao Liu; Qi Zhang; Hanyu Liu; Jia Zeng; Chengjie Ren; Gaihe Yang; Zekun Zhong; et al. (Journal of Environmental Management, 2023)

The PAVICS-Hydro platform: A virtual laboratory for hydroclimatic modelling and forecasting over North America - Richard Arsenault; David Huard; Jean-Luc Martel; Magali Troin; Juliane Mai; François Brissette; Christian Jauvin; Long Vu; James R. Craig; Trevor J. Smith; Travis Logan; Bryan A. Tolson; et al. (Environmental Modelling & Software, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Trace cisplatin and carboplatin removal by 3-mercaptopropionic acid and l-cysteine functionalized sponges: Adsorption behaviour and mechanism - Dong Han; Montserrat López-Mesas; Roberto Boada; Tania Farías; Ana R. Lazo Fraga; Manuel Valiente (Chemical Engineering Journal, 2023)

Are medication effects on subjective response to alcohol and cue-induced craving associated? A meta regression study - Lara A. Ray; Steven J. Nieto; Lindsay R. Meredith; Elizabeth Burnette; Suzanna Donato; Molly Magill; Han Du (Psychopharmacology, 2023)
Rationale Alcohol administration and cue-reactivity paradigms are frequently used to screen for the initial efficacy of medications for alcohol use disorder (AUD). While medication effects on the primary outcomes for these paradigms are assumed to be qualitatively related, there is a critical lack of quantitative evidence to support this hypothesis. Objectives The study aims to test the relationship between medication effect sizes on subjective response to alcohol administration and medication effect sizes for cue-induced craving to cue exposure, using meta-analysis. Methods Systematic literature searches were conducted to identify randomized trials, wherein AUD medications were tested using the alcohol administration and/or cue-reactivity paradigms. From these studies, descriptive statistics were collected to compute medication effect sizes on the primary outcomes for each respective paradigm. With medication as the unit of analysis, medication effect sizes in alcohol administration studies were compared with medication effect sizes in cue-reactivity studies using the Williamson-York regression which allows for meta-regression across independent samples. Results Medication effect sizes on alcohol-induced stimulation and alcohol-induced craving were not significantly associated with medication effect sizes on cue-induced alcohol craving ( k stimulation = 10 medications, $$\widehat{β }=0.272 \left(SE=0.263\right), p=0.150$$ β ^ = 0.272 SE = 0.263 , p = 0.150 and k craving = 11 medications, $$\widehat{β }=0.217$$ β ^ = 0.217 (SE = 0.237), $$p=0.181$$ p = 0.181 ), respectively. Medication effect sizes on alcohol-induced sedation were significantly associated with medication effects on cue-induced craving ( k = 10 medications, $$\widehat{β }=-0.600$$ β ^ = - 0.600 (SE = 0.258), $$p=0.010$$ p = 0.010 ), such that medications that increased alcohol-induced sedation were more likely to reduce cue-induced alcohol craving. Conclusions With the exception of alcohol-induced sedation, there is little quantitative evidence of medication effects on subjective response domains measured during alcohol administration parallel medication effects on cue-induced alcohol craving. To provide additional context to the current study, future work should examine whether cue-reactivity findings predict clinical trial outcomes.

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Characterization and functional properties of pH- and heated time-induced aggregates from red lentil protein - Han Du; Yichen Lin; Catherine Stanton; Davor Daniloski; Emanuele Zannini; R. Paul Ross; Song Miao (Food Structure, 2023)

Lead change of a HIF-2α antagonist guided by multiparameter optimization and utilization of an Olp→π*Ar interaction - Paul M. Wehn; Song Yang; Jonas A. Grina; James P. Rizzi; Stephen T. Schlachter; Bin Wang; Rui Xu; Hanbiao Yang; Xinlin Du; Guangzhou Han; Keshi Wang; Robert M. Czerwinski; et al. (Medicinal Chemistry Research, 2023)

SARS-CoV-2 3CL-protease inhibitors derived from ML300: investigation of P1 and replacements of the 1,2,3-benzotriazole - Alice Hooper; Jonathan D. Macdonald; Brenna Reilly; Joshua Maw; Aidan P. Wirrick; Sang Hoon Han; A. Abigail Lindsey; Emma G. Rico; Todd Romigh; Christopher M. Goins; Nancy S. Wang; Shaun R. Stauffer (Medicinal Chemistry Research, 2023)

Variation of the photosynthesis and respiration response of filamentous algae (Oedogonium) acclimated to averaged seasonal temperatures and light exposure levels - Sulochana Pitawala; Zlatan Trifunovic; Joel R. Steele; Han-Chung Lee; Nicholas D. Crosbie; Peter J. Scales; Gregory J.O. Martin (Algal Research, 2023)

Effects of aluminum ion on particle sizes and surface charges of exopolysaccharides from Rhizobium tropici and pH effects - Steve L. Larson; John H. Ballard; Kauri A. Runge; Huimin Zhang; Benjamin R. Breland; Zachary H. Nick; Ethan Tyler Vroman; Charles A. Weiss; Fengxiang X. Han (Rhizosphere, 2023)

BasinMaker 3.0: A GIS toolbox for distributed watershed delineation of complex lake-river routing networks - Ming Han; Hongren Shen; Bryan A. Tolson; James R. Craig; Juliane Mai; Simon G.M. Lin; Nandita B. Basu; Frezer S. Awol (Environmental Modelling & Software, 2023)

AI-aided multiscale modeling of physiologically-significant blood clots - Yicong Zhu; Changnian Han; Peng Zhang; Guojing Cong; James R. Kozloski; Chih-Chieh Yang; Leili Zhang; Yuefan Deng (Computer Physics Communications, 2023)

Genome-wide identification and expression analysis of terpene synthases in Gossypium species in response to gossypol biosynthesis - Teame Gereziher Mehari; Hui Fang; Wenxiang Feng; Yuanyuan Zhang; Muhammad Jawad Umer; Jinlei Han; Allah Ditta; Muhammad K. R. Khan; Fang Liu; Kai Wang; Baohua Wang (Functional & Integrative Genomics, 2023)

Deep genome-wide divergences among species in White Cloud Mountain minnow Tanichthys albonubes (Cypriniformes: Tanichthyidae) complex: Conservation and species management implications - Chao Li; Han Xiao; Xiuxia Zhang; Hungdu Lin; Kathryn R. Elmer; Jun Zhao (Molecular Phylogenetics and Evolution, 2023)

Geochemical and thermodynamic constraints on Archean comagmatic volcanic and cumulate rocks from southern West Greenland - Lingyu Zhang; William R. Hyde; Christopher L. Kirkland; Yuesheng Han; Kristoffer Szilas (Geochimica et Cosmochimica Acta, 2023)

Effects of ethanol pretreatment on osteogenic activity and off-flavors in blue mussel (Mytilus edulis L.) enzymatic hydrolysates - Xinyu Qiao; Han Li; Yunjiao Ma; Xianbing Xu; Junjie Yi; Hesham R. El-Seedi; Ming Du (Food Research International, 2023)

MXene/MnO2 nanocomposite coated superior salt-rejecting biodegradable luffa sponge for efficient solar steam generation - Ahmed Mortuza Saleque; Sainan Ma; Amrit Kumar Thakur; R. Saidur; Tan Kim Han; Mohammad Ismail Hossain; Wayesh Qarony; Y. Ma; Ravishankar Sathyamurthy; Yuen Hong Tsang (Desalination, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

Galectin-3-centered paracrine network mediates cardiac inflammation and fibrosis upon β-adrenergic insult - Guomin Hu; Jimin Wu; Huijun Gu; Xiangning Deng; Wenli Xu; Shan Feng; Shuaixing Wang; Yao Song; Zhengda Pang; Xiuling Deng; Aleksandr E. Vendrov; Nageswara R. Madamanchi; et al. (Science China Life Sciences, 2023)

Water trading as a tool to combat economic losses in agriculture under climate change - Xiaoliang Han; Proloy Deb; Nicholas R. Magliocca; Denis Nadolnyak; Hamed Moftakhari; Ruchie Pathak; Hamid Moradkhani (Sustainability Science, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Life cycle-carbon footprints for environmental performance/labeling of crop-based food products: analyses of complementary functional units and hotspots - N. C. O; S. C. Pak; R. J. Ri; H. I. Han (International Journal of Environmental Science and Technology, 2023)

β‐diversity in temperate grasslands is driven by stronger environmental filtering of plant species with large genomes - Hai‐Yang Zhang; Xiao‐Tao Lü; Cun‐Zheng Wei; Jeff R. Powell; Xiao‐Bo Wang; Ding‐Liang Xing; Zhu‐Wen Xu; Huan‐Long Li; Xing‐Guo Han (Ecology, 2023)
Elucidating mechanisms underlying community assembly and biodiversity patterns is central to ecology and evolution. Genome size (GS) has long been hypothesized to potentially affect species' capacity to tolerate environmental stress and might therefore help drive community assembly. However, its role in driving β‐diversity (i.e., spatial variability in species composition) remains unclear. We measured GS for 161 plant species and community composition across 52 sites spanning a 3200‐km transect in the temperate grasslands of China. By correlating the turnover of species composition with environmental dissimilarity, we found that resource filtering (i.e., environmental dissimilarity that includes precipitation, and soil nitrogen and phosphorus concentrations) affected β‐diversity patterns of large‐GS species more than small‐GS species. By contrast, geographical distance explained more variation of β‐diversity for small‐GS than for large‐GS species. In a 10‐year experiment manipulating levels of water, nitrogen, and phosphorus, adding resources increased plant biomass in species with large GS, suggesting that large‐GS species are more sensitive to the changes in resource availability. These findings highlight the role of GS in driving community assembly and predicting species responses to global change.

Alkaline ball-milled peanut-hull biosorbent effectively removes aqueous organic dyes - Xiaodong Yang; Lili Wang; Jin Tong; Xueqin Shao; Ying Feng; Jinfeng Zhou; Ye Han; Xizhen Yang; Fangjun Ding; Jing Zhang; Qiaoyu Li; Guodong Li; et al. (Chemosphere, 2023)

SMAP soil moisture data assimilation impacts on water quality and crop yield predictions in watershed modeling - Garett Pignotti; Melba Crawford; Eunjin Han; Mark R. Williams; Indrajeet Chaubey (Journal of Hydrology, 2023)

Assessment of the inhibitive performance of a hydrazone derivative for steel rebar in a simulated concrete medium: Establishing the inhibition mechanism at an experimental and theoretical level - Karthick Subbiah; Han-Seung Lee; Mustafa R. Al-Hadeethi; Taejoon Park; Hassane Lgaz (Chemical Engineering Journal, 2023)

Influence of catalase encapsulation on Cobalt@Nanoporous carbon with multiwall shell for supercapacitor and polyurethane synthesis using carbon dioxide - Rahul Patil; Nitish Kumar; Sudip Bhattacharjee; Hsi-Yen Wu; Po-Chun Han; Babasaheb M. Matsagar; Kevin C.W. Wu; Rahul R. Salunkhe; Asim Bhaumik; Saikat Dutta (Chemical Engineering Journal, 2023)

Comparison of Prospective and Retrospective Gated 4D Flow Cardiac MR Image Acquisitions in the Carotid Bifurcation - Elliott R. Hurd; Mengjiao Han; Jason K. Mendes; J. Rock Hadley; Chris R. Johnson; Edward V. R. DiBella; John N. Oshinski; Lucas H. Timmins (Cardiovascular Engineering and Technology, 2023)

Impacts of land uses on spatio-temporal variations of seasonal water quality in a regulated river basin, Huai River, China - Lingqing Wang; Xiaoxiao Han; Yongyong Zhang; Qian Zhang; Xiaoming Wan; Tao Liang; Hocheol Song; Nanthi Bolan; Sabry M. Shaheen; John R. White; Jörg Rinklebe (Science of The Total Environment, 2023)

Biodegradation of high di-(2-Ethylhexyl) phthalate (DEHP) concentration by food waste composting and its toxicity assessment using seed germination test - Huu-Tuan Tran; Chitsan Lin; Su Shiung Lam; Thi Hieu Le; Hong-Giang Hoang; Xuan-Thanh Bui; Eldon R. Rene; Po Han Chen (Environmental Pollution, 2023)

Incorporating field-based research into remote learning: An assessment of soil lead pollution in different land-use types in Los Angeles - Wei-Cheng Hung; Naomi Adams; Zanobia R. Ibrahim-Watkins; Dorothy Nguyen; Tricia Jain; Yu-Han Wang; Jennifer A. Jay (Environmental Research, 2023)

Rapid preparation of nickel fluoride motif via solution-free plasma route for high-energy aqueous hybrid supercapacitor - Nilesh R. Chodankar; Indrajit V. Bagal; Swati J. Patil; Seung-Kyu Hwang; Pragati A. Shinde; Amar M. Patil; Smita V. Karekar; Amal Al Ghaferi; Wenli Zhang; Sang-Wan Ryu; Yun Suk Huh; Young Kyu Han (Chemical Engineering Journal, 2023)

Gastrointestinal consequences of lipopolysaccharide-induced lung inflammation - Rachel M. McQuade; Methma Bandara; Shanti Diwakarla; Lauren Sahakian; Myat Noe Han; Maryam Al Thaalibi; Madeleine R. Di Natale; Marsha Tan; Kiera H. Harwood; Elena K. Schneider-Futschik; Andrew Jarnicki (Inflammation Research, 2023)
Background Respiratory inflammation is the body’s response to lung infection, trauma or hypersensitivity and is often accompanied by comorbidities, including gastrointestinal (GI) symptoms. Why respiratory inflammation is accompanied by GI dysfunction remains unclear. Here, we investigate the effect of lipopolysaccharide (LPS)-induced lung inflammation on intestinal barrier integrity, tight-junctions, enteric neurons and inflammatory marker expression. Methods Female C57bl/6 mice (6–8 weeks) were intratracheally administered LPS (5 µg) or sterile saline, and assessed after either 24 or 72 h. Total and differential cell counts in bronchoalveolar lavage fluid (BALF) were used to evaluate lung inflammation. Intestinal barrier integrity was assessed via cross sectional immunohistochemistry of tight junction markers claudin-1, claudin-4 and EpCAM. Changes in the enteric nervous system (ENS) and inflammation in the intestine were quantified immunohistochemically using neuronal markers Hu + and nNOS, glial markers GFAP and S100β and pan leukocyte marker CD45. Results Intratracheal LPS significantly increased the number of neutrophils in BALF at 24 and 72 h. These changes were associated with an increase in CD45 + cells in the ileal mucosa at 24 and 72 h, increased goblet cell expression at 24 h, and increased expression of EpCAM at 72 h. LPS had no effect on the expression of GFAP, S100β, nor the number of Hu + neurons or proportion of nNOS neurons in the myenteric plexus. Conclusions Intratracheal LPS administration induces inflammation in the ileum that is associated with enhanced expression of EpCAM, decreased claudin-4 expression and increased goblet cell density, these changes may contribute to systemic inflammation that is known to accompany many inflammatory diseases of the lung.

The developmental journey of therapies targeting purine receptors: from basic science to clinical trials - Seunga Han; Haruna Suzuki-Kerr; Srdjan M. Vlajkovic; Peter R. Thorne (Purinergic Signalling, 2022)
Since the discovery of ATP as an extracellular signalling molecule in 1972, purinergic signalling, mediated by extracellular purines and pyrimidines has been identified in virtually all mammalian tissues and is implicated in regulating fundamental cellular processes. In recent years, there has been an increasing focus on the pathophysiology and potential therapeutic interventions based on purinergic signalling. A vast range of compounds targeting purine receptors are in clinical development, and many more are in preclinical studies, which highlights the fast growth in this research field. As a tribute to Professor Geoffrey Burnstock’s legacy in purinergic signalling, we present here a brief review of compounds targeting purine receptors that are in different stages of clinical trials. The review highlights the 50-year journey from basic research on purinergic receptors to clinical applications of therapies targeting purine receptors.

Lifestyle intervention program reduces metabolic syndrome in a high-risk population - Ronda R. Davis; Hyo-Jeong Hwang; Easton A. Reid; Kyoung-Sik Han (Toxicology and Environmental Health Sciences, 2022)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Patient Perspectives on the Risk-Based NLST Outcomes Tool for Lung Cancer Screening - Megan C. Roberts; Elizabeth L. Seaman; William M. P. Klein; Rebecca A. Ferrer; Paul K.J. Han; Hormuzd A. Katki; Stephanie R. Land; Robert A. Liotta; Joel A. Nations; P. Gabriel Peterson (Journal of Cancer Education, 2022)

Sustained-release ketamine-loaded lipid-particulate system: in vivo assessment in mice - Weizhi Xu; Faheem Maqbool; Vinod Kumar; James R. Falconer; Cedric S. Cui; Trent M. Woodruff; Karin Borges; Andrew K. Whittaker; Maree T. Smith; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

Advancements of nature nanocage protein: preparation, identification and multiple applications of ferritins - Han Li; Xiaoyu Xia; Xiaoyi Tan; Jiachen Zang; Zhenyu Wang; Hesham R. EI-Seedi; Ming Du (Critical Reviews in Food Science and Nutrition, 2022)

Inter- and intra-species heterogeneity in germination of Aspergillus conidia - Maryam Ijadpanahsaravi; Wieke R. Teertstra; Han A. B. Wösten (Antonie van Leeuwenhoek, 2022)
Aspergilli are among the most abundant fungi worldwide. They degrade organic material and can be pathogens of plants and animals. Aspergilli spread by forming high numbers of conidia. Germination of these stress resistant asexual spores is characterized by a swelling and a germ tube stage. Here, we show that conidia of Aspergillus niger, Aspergillus oryzae, Aspergillus clavatus , Aspergillus nidulans and Aspergillus terreus show different swelling and germ tube formation dynamics in pure water or in water supplemented with (in)organic nutrients. Apart from inter-species heterogeneity, intra-species heterogeneity was observed within spore populations of the aspergilli except for A. terreus . Sub-populations of conidia differing in size and/or contrast showed different swelling and germ tube formation dynamics. Together, data imply that aspergilli differ in their competitive potential depending on the substrate. Moreover, results suggest that intra-species heterogeneity provides a bet hedging mechanism to optimize survival of aspergilli.

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables - Jessica L. Gronniger; Zhao Wang; Genevieve R. Brandt; Christopher S. Ward; Despina Tsementzi; Han Mu; Junyao Gu; Zackary I. Johnson; Konstantinos T. Konstantinidis; Dana E. Hunt (Environmental Microbiology, 2022)
Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest week‐over‐week changes in the microbiome (i.e. identifying disturbance as events that alter the community composition). In general, these microbiome disturbances were not clearly linked to specific environmental factors and responsive taxa largely differed, aside from SAR11, which generally declined. However, several disturbance metagenomes identified increased phage‐associated genes, suggesting that unexplained community shifts might be caused by increased mortality. Furthermore, a category 1 hurricane, the only event that would likely be classified a priori as an environmental disturbance, was not an outlier in microbiome composition, but did enhance a bloom in seasonally abundant phytoplankton. Thus, as extreme environmental changes intensify, assumptions of what constitutes a disturbance should be re‐examined in the context of ecological history and microbiome responses.

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Data-driven approaches for runoff prediction using distributed data - Heechan Han; Ryan R. Morrison (Stochastic Environmental Research and Risk Assessment, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Integrative epigenomic and transcriptomic analyses reveal metabolic switching by intermittent fasting in brain - Gavin Yong-Quan Ng; Dominic Paul Lee Kok Sheng; Han-Gyu Bae; Sung Wook Kang; David Yang-Wei Fann; Jinsu Park; Joonki Kim; Asfa Alli-Shaik; Jeongmi Lee; Eunae Kim; Sunyoung Park; Jeung-Whan Han; et al. (GeroScience, 2022)

Truncation of the N-terminus of cardiac troponin I initiates adaptive remodeling of the myocardial proteosome via phosphorylation of mechano-sensitive signaling pathways - Chad M. Warren; Monika Halas; Paul H. Goldspink; Han-Zhong Feng; Anthony W. Herren; Beata M. Wolska; Pieter P. de Tombe; Jian-Ping Jin; R. John Solaro (Molecular and Cellular Biochemistry, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Investigation on redox status and gene expression related to larval cryopreservation in the Pacific oyster Crassostrea gigas - Yibing Liu; Xin Zhan; Sarah R. Catalano; Jianguang Qin; Jiabo Han; Xiaoxu Li (Fisheries Science, 2022)

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

Penicillium roqueforti conidia induced by L-amino acids can germinate without detectable swelling - Maarten Punt; Wieke R. Teertstra; Han A. B. Wösten (Antonie van Leeuwenhoek, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

Molecular characterization of Toll-like receptor type-3 in mallard duck and its response to Newcastle disease virus infection - Wael K. Elfeil; Reham R. Abouelmaatti; Shaimaa Talat; Mohamed Fawzy; Mohamed Rady; Mohamed Diab; Saad Alkahtani; Hesham Sultan; Changjiang Sun; Liancheng Lei; Wenyu Han; Mahmoud Sedeik; et al. (Environmental Science and Pollution Research, 2021)

Eutrophication and Hypoxia in Tropical Negombo Lagoon, Sri Lanka - Hsueh-Han Hsieh; Ming-Hsiu Chuang; Yung-Yen Shih; W. Sanjaya Weerakkody; Wei-Jen Huang; Chin-Chang Hung; François L. L. Muller; R. R. M. K. P. Ranatunga; D. S. Wijethunga (Frontiers in Marine Science, 2021)
Hypoxic events are becoming frequent in some estuaries and coastal waters due to over-enrichment of anthropogenic nutrients, organic matter, and/or due to restricted water circulation. The coastal lagoons and estuaries of Sri Lanka are facing high population pressure and lacking sufficient infrastructure. Coastal lagoons may receive high anthropogenic inputs of natural or untreated nitrogen and phosphorus wastes, and consequently result in hypoxic conditions while sluggish circulation occurred. In this study, we examined the spatiotemporal variability of eutrophication and hypoxia in the Negombo Lagoon, one of the most productive and sensitive coastal ecosystems in Sri Lanka. Based on seasonal measurements of dissolved oxygen, nutrients, chlorophyll- a (Chl- a ), particulate and dissolved organic carbon (POC and DOC), we concluded that eutrophication and hypoxia occurred in both the dry and wet seasons. The main contributing factors were high seawater temperature and poor water circulation in the dry season and high nutrient loading combined with elevated POC and DOC inputs in the wet season.

Correction to: Identification and molecular characterization of tea‑oil camellia‑associated totivirus 1 - Z.-Y. Zhang; H. Huang; X. X. Han; R. Li; L.-P. Wu; L. Wu (Archives of Virology, 2021)

Identification and molecular characterization of tea-oil camellia-associated totivirus 1 - Z.-Y. Zhang; H. Huang; X. X. Han; R. Li; L.-P. Wu; L. Wu (Archives of Virology, 2021)

Loss of endothelial glucocorticoid receptor promotes angiogenesis via upregulation of Wnt/β-catenin pathway - Bing Liu; Han Zhou; Tiening Zhang; Xixiang Gao; Bo Tao; Hao Xing; Zhenwu Zhuang; Alan Dardik; Themis R. Kyriakides; Julie E. Goodwin (Angiogenesis, 2021)
Objective The glucocorticoid receptor (GR) is a member of the nuclear receptor family that controls key biological processes in the cardiovascular system and has recently been shown to modulate Wnt signaling in endothelial cells. Wnt/β-catenin signaling has been demonstrated to be crucial in the process of angiogenesis. In the current study, we studied whether GR could regulate angiogenesis via the Wnt/β-catenin pathway. Approach and Resultsa Key components of the Wnt/β-catenin pathway were evaluated using quantitative PCR and Western blot in the presence or absence of GR. Enhanced angiogenesis was found in GR deficiency in vitro and confirmed with cell viability assays, proliferation assays and tube formation assays. Consistent with these in vitro findings, endothelial cell-specific GR loss GR in vivo promoted angiogenesis in both a hind limb ischemia model and sponge implantation assay. Results were further verified in a novel mouse model lacking endothelial LRP5/6, a key receptor in canonical Wnt signaling, and showed substantially suppressed angiogenesis using these same in vitro and in vivo assays. To further investigate the mechanism of GR regulation of Wnt signaling, autophagy flux was investigated in endothelial cells by visualizing auto phagolysosomes as well as by assessing P62 degradation and LC3B conversion. Results indicated that potentiated autophagy flux participated in GR-Wnt regulation. Conclusions Lack of endothelial GR triggers autophagy flux, leads to activation of Wnt/β-catenin signaling and promotes angiogenesis. There may also be a synergistic interaction between autophagy and Wnt/β-catenin signaling.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

Global soil‐derived ammonia emissions from agricultural nitrogen fertilizer application: A refinement based on regional and crop‐specific emission factors - Ruoya Ma; Jianwen Zou; Zhaoqiang Han; Kai Yu; Shuang Wu; Zhaofu Li; Shuwei Liu; Shuli Niu; William R. Horwath; Xia Zhu‐Barker (Global Change Biology, 2021)
Ammonia (NH 3 ) emissions from fertilized soils to the atmosphere and the subsequent deposition to land surface exert adverse effects on biogeochemical nitrogen (N) cycling. The region‐ and crop‐specific emission factors (EFs) of N fertilizer for NH 3 are poorly developed and therefore the global estimate of soil NH 3 emissions from agricultural N fertilizer application is constrained. Here we quantified the region‐ and crop‐specific NH 3 EFs of N fertilizer by compiling data from 324 worldwide manipulative studies and focused to map the global soil NH 3 emissions from agricultural N fertilizer application. Globally, the NH 3 EFs averaged 12.56% and 14.12% for synthetic N fertilizer and manure, respectively. Regionally, south‐eastern Asia had the highest NH 3 EFs of synthetic N fertilizer (19.48%) and Europe had the lowest (6%), which might have been associated with the regional discrepancy in the form and rate of N fertilizer use and management practices in agricultural production. Global agricultural NH 3 emissions from the use of synthetic N fertilizer and manure in 2014 were estimated to be 12.32 and 3.79 Tg N/year, respectively. China (4.20 Tg N/year) followed by India (2.37 Tg N/year) and America (1.05 Tg N/year) together contributed to over 60% of the total global agricultural NH 3 emissions from the use of synthetic N fertilizer. For crop‐specific emissions, the NH 3 EFs averaged 11.13%–13.95% for the three main staple crops (i.e., maize, wheat, and rice), together accounting for 72% of synthetic N fertilizer‐induced NH 3 emissions from croplands in the world and 70% in China. The region‐ and crop‐specific NH 3 EFs of N fertilizer established in this study offer references to update the default EF in the IPCC Tier 1 guideline. This work also provides an insight into the spatial variation of soil‐derived NH 3 emissions from the use of synthetic N fertilizer in agriculture at the global and regional scales.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Dynamic network connectivity predicts subjective cognitive decline: the Sino-Longitudinal Cognitive impairment and dementia study - Guozhao Dong; Liu Yang; Chiang-shan R. Li; Xiaoni Wang; Yihe Zhang; Wenying Du; Ying Han; Xiaoying Tang (Brain Imaging and Behavior, 2020)

Anthropogenic Contaminants and Histopathological Findings in Stranded Cetaceans in the Southeastern United States, 2012–2018 - Annie Page-Karjian; Catherine F. Lo; Branson Ritchie; Craig A. Harms; David S. Rotstein; Sushan Han; Sayed M. Hassan; Andreas F. Lehner; John P. Buchweitz; Victoria G. Thayer; Jill M. Sullivan; Emily F. Christiansen; et al. (Frontiers in Marine Science, 2020)

How changing cloud water to rain conversion profile impacts on radiation and its linkage to a better Indian summer monsoon rainfall simulation - Tanmoy Goswami; Parthasarathi Mukhopadhyay; Malay Ganai; R. Phani Murali Krishna; Mata Mahakur; Ji-Young Han (Theoretical and Applied Climatology, 2020)

Multiomic immune clockworks of pregnancy - Laura S. Peterson; Ina A. Stelzer; Amy S. Tsai; Mohammad S. Ghaemi; Xiaoyuan Han; Kazuo Ando; Virginia D. Winn; Nadine R. Martinez; Kevin Contrepois; Mira N. Moufarrej; Stephen Quake; David A. Relman; et al. (Seminars in Immunopathology, 2020)
Preterm birth is the leading cause of mortality in children under the age of five worldwide. Despite major efforts, we still lack the ability to accurately predict and effectively prevent preterm birth. While multiple factors contribute to preterm labor, dysregulations of immunological adaptations required for the maintenance of a healthy pregnancy is at its pathophysiological core. Consequently, a precise understanding of these chronologically paced immune adaptations and of the biological pacemakers that synchronize the pregnancy “immune clock” is a critical first step towards identifying deviations that are hallmarks of peterm birth. Here, we will review key elements of the fetal, placental, and maternal pacemakers that program the immune clock of pregnancy. We will then emphasize multiomic studies that enable a more integrated view of pregnancy-related immune adaptations. Such multiomic assessments can strengthen the biological plausibility of immunological findings and increase the power of biological signatures predictive of preterm birth

A Facile and Sensitive DNA Sensing of Harmful Algal Blooms Based on Graphene Oxide Nanosheets - Le Qiang; Yu Zhang; Chao Wu; Yingkuan Han; Suchun Wang; Yanyan Wang; Congcong Zhang; Guangzhou Liu; Qi Wu; Hong Liu; Ian R. Jenkinson; Jun Sun; et al. (Marine Biotechnology, 2020)

Revisiting the plant growth-promoting rhizobacteria: lessons from the past and objectives for the future - Abhinav Aeron; Ekta Khare; Chaitanya Kumar Jha; Vijay Singh Meena; Shadia Mohammed Abdel Aziz; Mohammed Tofazzal Islam; Kangmin Kim; Sunita Kumari Meena; Arunava Pattanayak; Hosahatti Rajashekara; Ramesh Chandra Dubey; Bihari Ram Maurya; et al. (Archives of Microbiology, 2020)

Herbul black henna (hair dye) causes cardiovascular defects in zebrafish (Danio rerio) embryo model - Bangeppagari Manjunatha; Liwen Han; Rajesh R. Kundapur; Kechun Liu; Sang Joon Lee (Environmental Science and Pollution Research, 2020)

Nonlinear responses of soil nematode community composition to increasing aridity - Dan Xiong; CunZheng Wei; E. R. Jasper Wubs; G. F. Veen; Wenju Liang; Xiaobo Wang; Qi Li; Wim H. Van der Putten; Xingguo Han (Global Ecology and Biogeography, 2020)
Aim Increasing aridity under global change is predicted to have a profound impact on the structure and functioning of terrestrial ecosystems, yet we have a poor understanding of how belowground communities respond. In order to understand the longer term responses of different trophic levels in the soil food web to increasing aridity, we investigated the abundance, richness and community similarity of the soil nematode community along a 3,200 km aridity gradient. Location A transect across semi‐arid and arid grasslands in Northern China, where the aridity ranges from .43 to .97. Time period July and August 2012. Major taxa studied Soil‐borne Nematoda. Methods We used generalized additive (mixed) models to analyse the abundance, richness and community similarity patterns of soil nematodes. We used structural equation modelling (SEM) to disentangle the direct and indirect environmental drivers (aridity, soil and plant variables) of the nematode community. Results The abundance, richness and similarity of nematode communities declined nonlinearly with increasing aridity. The most pronounced decline in nematode richness and community similarity occurred in arid conditions (aridity > .80). However, the shape of the response to aridity differed among nematode feeding groups. In arid conditions, the abundance and richness of bacterial feeders were less sensitive to changes in aridity than for fungal feeders. The SEM analysis revealed that nematode community responses to aridity were not mediated via changes in plant and soil variables, but instead were affected directly by aridity. Main conclusions Our results showed that in mesic grasslands, increasing aridity primarily caused a decline in nematode abundance, whereas increasing aridity in xeric grasslands led to a loss of nematode diversity. The nonlinear responses of nematodes to aridity could also result in nonlinear shifts in ecosystem functioning, because soil nematodes operate at various trophic levels in the soil food web, thereby influencing the performance of plants, soil biodiversity and biogeochemical cycling.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Consensus Paper: Experimental Neurostimulation of the Cerebellum - Lauren N. Miterko; Kenneth B. Baker; Jaclyn Beckinghausen; Lynley V. Bradnam; Michelle Y. Cheng; Jessica Cooperrider; Mahlon R. DeLong; Simona V. Gornati; Mark Hallett; Detlef H. Heck; Freek E. Hoebeek; Abbas Z. Kouzani; et al. (The Cerebellum, 2019)

Development of In Vitro–In Vivo Correlation for Upadacitinib Extended-Release Tablet Formulation - Mohamed-Eslam F. Mohamed; Sheryl Trueman; Ahmed A. Othman; Jian-Hwa Han; Tzuchi R. Ju; Patrick Marroum (The AAPS Journal, 2019)
Upadacitinib is a selective Janus Kinase 1 inhibitor which is being developed for the treatment of several inflammatory diseases including rheumatoid arthritis. Upadacitinib was evaluated in Phase 3 studies as an oral extended-release (ER) formulation administered once daily. The purpose of this study was to develop a level A in vitro – in vivo correlation (IVIVC) for upadacitinib ER formulation. The pharmacokinetics of four upadacitinib extended-release formulations with different in vitro release characteristics and an immediate-release capsule formulation of upadacitinib were evaluated in 20 healthy subjects in a single-dose, randomized, crossover study. In vivo pharmacokinetic data and in vitro dissolution data (USP Dissolution Apparatus 1; pH 6.8; 100 rpm) were used to establish a level A IVIVC. Three formulations were used to establish the IVIVC, and the fourth formulation was used for external validation. A non-linear IVIVC best described the relationship between upadacitinib in vitro dissolution and in vivo absorption profiles. The absolute percent prediction errors (%PE) for upadacitinib C max and AUC were less than 10% for all three formulations used to establish the IVIVC, as well as for the %PE for the external validation formulation and the overall mean internal validation. Model was cross-validated using the leave-one-out approach; all evaluated cross-validation runs met the regulatory acceptance criteria. A level A IVIVC was successfully developed and validated for upadacitinib ER formulation, which meets the FDA and EMA regulatory validation criteria and can be used as surrogate for in vivo bioequivalence.

Tuta absoluta continues to disperse in Asia: damage, ongoing management and future challenges - Peng Han; Yunus Bayram; Liora Shaltiel-Harpaz; Fariba Sohrabi; Anitha Saji; Uulu Tair Esenali; Anvar Jalilov; Abid Ali; Pathour R. Shashank; Khasan Ismoilov; Zhao-zhi Lu; Su Wang; et al. (Journal of Pest Science, 2019)

Increased Diagnostic Yield of Spastic Paraplegia with or Without Cerebellar Ataxia Through Whole-Genome Sequencing - Aryun Kim; Kishore R. Kumar; Ryan L. Davis; Amali C. Mallawaarachchi; Velimir Gayevskiy; Andre E. Minoche; Zachary Walls; Han-Joon Kim; Mihee Jang; Mark J. Cowley; Ji-Hyun Choi; Chaewon Shin; et al. (The Cerebellum, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

A high production of flavonoids and anthraquinones via adventitious root culture of Oplopanax elatus and evaluating antioxidant activity - L. Han; X. C. Piao; J. Jiang; X. L. Jiang; C. R. Yin; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Dietary choline and betaine intakes and risk of total and lethal prostate cancer in the Atherosclerosis Risk in Communities (ARIC) Study - Peijin Han; Aurelian Bidulescu; John R. Barber; Steven H. Zeisel; Corinne E. Joshu; Anna E. Prizment; Mara Z. Vitolins; Elizabeth A. Platz (Cancer Causes & Control, 2019)

Diversity and evolution of cytochromes P450 in stramenopiles - Linhong Teng; Xiao Fan; David R. Nelson; Wentao Han; Xiaowen Zhang; Dong Xu; Hugues Renault; Gabriel V. Markov; Naihao Ye (Planta, 2019)

Assessing connectivity patterns among management units of the Newfoundland and Labrador shrimp population - Nicolas Le Corre; Pierre Pepin; Guoqi Han; Zhimin Ma; Paul V. R. Snelgrove (Fisheries Oceanography, 2019)
The Eastern Canadian northern shrimp population, representing one of the most important fisheries in the region, decreased dramatically since the mid‐2000s to a historical low in 2017, but changes were not spatially uniform. Applying a biophysical model within Newfoundland and Labrador ( NL ) management areas, we investigated connectivity processes during the long pelagic larval phase (2–3 months) of Pandalus borealis and key drivers of larval dispersal in different environmental conditions. We selected 3 years representative of contrasting North Atlantic Oscillation ( NAO ) phases to assess potential larval dispersal patterns of the northern shrimp population in NL , and hierarchically assessed the impact of the timing of release (yearly and daily), release location, and vertical migration behaviour on shrimp larval dispersal. Overall, we found that populations located on the northern Newfoundland and Labrador shelf supplied potential settlers to southern populations because of the dominant Labrador Current. Ocean circulation and current velocities during the NAO positive year differed from other years, generating contrasting settlement spatial patterns. Larval release location and vertical migration behaviour were the two most important influences on the strength of larval supply and settlement patterns. Inclusion of diel and ontogenic swimming behaviour increased settlement success of larvae released from inshore areas, regardless of study years. Our study improves understanding of northern shrimp stock‐recruitment relationships, their sensitivity to changing environmental conditions, and spatially non‐homogeneous population decline for bentho‐pelagic species with a long larval phase, which could potentially help improve management strategies.

Modeling fully coupled hydraulic-mechanical-chemical processes in a natural clay liner under mechanical and chemico-osmotic consolidation - Zhihong Zhang; Shakil A. Masum; Hywel R. Thomas; Lin Han (Environmental Science and Pollution Research, 2018)

Detecting hydrological consistency between soil moisture and precipitation and changes of soil moisture in summer over the Tibetan Plateau - X. Meng; R. Li; L. Luan; S. Lyu; T. Zhang; Y. Ao; B. Han; L. Zhao; Y. Ma (Climate Dynamics, 2018)

Transcriptomic analysis of porcine PBMCs in response to Actinobacillus pleuropneumoniae reveals the dynamic changes of differentially expressed genes related to immuno-inflammatory responses - Hexiang Jiang; Rining Zhu; Hongtao Liu; Chuntong Bao; Jianfang Liu; Abdalla Eltahir; Paul R. Langford; Diangang Sun; Zhonghua Liu; Changjiang Sun; Jingmin Gu; Wenyu Han; et al. (Antonie van Leeuwenhoek, 2018)

Gauging support for macroecological patterns in helminth parasites - Tad A. Dallas; A. Alonso Aguirre; Sarah Budischak; Colin Carlson; Vanessa Ezenwa; Barbara Han; Shan Huang; Patrick R. Stephens (Global Ecology and Biogeography, 2018)
Aim To explore spatial patterns of helminth parasite diversity, and to investigate three main macroecological patterns – (a) latitude–diversity relationships, (b) positive scaling between parasite and host diversity, and (c) species–area relationships – using a largely underutilized global database of helminth parasite occurrence records. Location Global. Methods We examined the London Natural History Museum’s collection of helminth parasite occurrence records, consisting of over 18,000 unique host species and 27,000 unique helminth parasite species distributed across over 350 distinct terrestrial and aquatic localities. Results We find support for latitudinal gradients in parasite diversity and a strong relationship between host and parasite diversity at the global scale. Helminth species diversity–area relationships were not detectable as a function of host body mass, but larger geographic areas supported higher parasite richness, potentially mediated through higher host richness. Main conclusions Our findings indicate that helminth parasites may obey some of the macroecological relationships found in free‐living species, suggesting that parasites may offer further support for the generality of these patterns, while offering interesting counterexamples for others. We conclude with a discussion of future directions and potential challenges in the newly emerging macroecology of infectious disease.

Influences of U Sources and Forms on Its Bioaccumulation in Indian Mustard and Sunflower - Fande Meng; Decheng Jin; Kai Guo; Steven L. Larson; John H. Ballard; Liangmei Chen; Zikri Arslan; Guodong Yuan; Jeremy R. White; Lixiang Zhou; Youhua Ma; Charles A. Waggoner; et al. (Water, Air, & Soil Pollution, 2018)

Optimization of culture medium components and culture period for production of adventitious roots of Echinacea pallida (Nutt.) Nutt - Y. Gao; C. H. Wu; X. C. Piao; L. Han; R. Gao; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Fluorescent reporter transgenic mice for in vivo live imaging of angiogenesis and lymphangiogenesis - Susan J. Doh; Michael Yamakawa; Samuel M. Santosa; Mario Montana; Kai Guo; Joseph R. Sauer; Nicholas Curran; Kyu-Yeon Han; Charles Yu; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; et al. (Angiogenesis, 2018)

Clinical Translation of the LevelCheck Decision Support Algorithm for Target Localization in Spine Surgery - Amir Manbachi; Tharindu De Silva; Ali Uneri; Matthew Jacobson; Joseph Goerres; Michael Ketcha; Runze Han; Nafi Aygun; David Thompson; Xiaobu Ye; Sebastian Vogt; Gerhard Kleinszig; et al. (Annals of Biomedical Engineering, 2018)

Effect of intermediate disturbance on soil microbial functional diversity depends on the amount of effective resources - Ximei Zhang; Eric R. Johnston; Albert Barberán; Yi Ren; Zhiping Wang; Xingguo Han (Environmental Microbiology, 2018)
Summary Many anthropogenic environmental changes are leading to a rapid decline in soil microbial functional diversity. However, ecological mechanisms that can serve to counteract/resist the diversity loss remain largely underexplored. In particular, although intermediate disturbance and increased amount of effective resources can promote the diversity of higher organisms, the potential role of these factors, and their combination, in maintaining microbial functional diversity is poorly studied. We conducted a 5‐year experiment in a Eurasian steppe, manipulating mowing, nitrogen addition, phosphorus addition and their combinations. Nitrogen addition decreased soil pH by ~0.6 and bacterial abundance by ~19.5%, causing a disturbance effect. Phosphorus addition significantly decreased the effective amount of soil carbon‐, nitrogen‐, phosphorus‐ and water‐relevant resources. Across all nitrogen‐addition treatments subject to intermediate disturbance, there was a significant positive correlation between soil effective resource amount and microbial gene richness ( r > 0.6, p

Carbon Storage Declines in Old Boreal Forests Irrespective of Succession Pathway - Bilei Gao; Anthony R. Taylor; Eric B. Searle; Praveen Kumar; Zilong Ma; Alexandra M. Hume; Han Y. H. Chen (Ecosystems, 2018)

Winter hatching in New England populations of invasive pheretimoid earthworms Amynthas agrestis and Amynthas tokioensis: a limit on population growth, or aid in peripheral expansion? - Josef H. Görres; Samantha T. Connolly; Chih-Han Chang; Nell R. Carpenter; Erin L. Keller; Maryam Nouri-Aiin; Joseph J. Schall (Biological Invasions, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Effect of Cu(II) on the stability of oxyanion-substituted schwertmannite - Junfei Li; Yingying Xie; Guining Lu; Han Ye; Xiaoyun Yi; John R. Reinfelder; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Co-invasion of three Asian earthworms, Metaphire hilgendorfi, Amynthas agrestis and Amynthas tokioensis in the USA - Chih-Han Chang; Marie R. Johnston; Josef H. Görres; Andrea Dávalos; Damhnait McHugh; Katalin Szlavecz (Biological Invasions, 2018)

Rhizosphere‐associated Pseudomonas induce systemic resistance to herbivores at the cost of susceptibility to bacterial pathogens - Cara H. Haney; Christina L. Wiesmann; Lori R. Shapiro; Ryan A. Melnyk; Lucy R. O'Sullivan; Sophie Khorasani; Li Xiao; Jiatong Han; Jenifer Bush; Juli Carrillo; Naomi E. Pierce; Frederick M. Ausubel (Molecular Ecology, 2018)
Plant‐associated soil microbes are important mediators of plant defence responses to diverse above‐ground pathogen and insect challengers. For example, closely related strains of beneficial rhizosphere Pseudomonas spp. can induce systemic resistance ( ISR ), systemic susceptibility ( ISS ) or neither against the bacterial foliar pathogen Pseudomonas syringae pv. tomato DC 3000 ( Pto DC 3000). Using a model system composed of root‐associated Pseudomonas spp. strains, the foliar pathogen Pto DC 3000 and the herbivore Trichoplusia ni (cabbage looper), we found that rhizosphere‐associated Pseudomonas spp. that induce either ISS and ISR against Pto DC 3000 all increased resistance to herbivory by T. ni . We found that resistance to T. ni and resistance to Pto DC 3000 are quantitative metrics of the jasmonic acid ( JA )/salicylic acid ( SA ) trade‐off and distinct strains of rhizosphere‐associated Pseudomonas spp. have distinct effects on the JA / SA trade‐off. Using genetic analysis and transcriptional profiling, we provide evidence that treatment of Arabidopsis with Pseudomonas sp. CH 267, which induces ISS against bacterial pathogens, tips the JA / SA trade‐off towards JA ‐dependent defences against herbivores at the cost of a subset of SA ‐mediated defences against bacterial pathogens. In contrast, treatment of Arabidopsis with the ISR strain Pseudomonas sp. WCS 417 disrupts JA / SA antagonism and simultaneously primes plants for both JA ‐ and SA ‐mediated defences. Our findings show that ISS against the bacterial foliar pathogens triggered by Pseudomonas sp. CH 267 , which is a seemingly deleterious phenotype, may in fact be an adaptive consequence of increased resistance to herbivory. Our work shows that pleiotropic effects of microbiome modulation of plant defences are important to consider when using microbes to modify plant traits in agriculture.

Correction to: Effects of Moisture-Induced Crystallization on the Aerosol Performance of Spray Dried Amorphous Ciprofloxacin Powder Formulations - Nivedita Shetty; Lingfei Zeng; Sharad Mangal; Haichen Nie; Matthew R. Rowles; Rui Guo; Youngwoo Han; Joon Hyeong Park; Qi Zhou (Pharmaceutical Research, 2018)

The FlbA-regulated predicted transcription factor Fum21 of Aspergillus niger is involved in fumonisin production - David Aerts; Esther E. Hauer; Robin A. Ohm; Mark Arentshorst; Wieke R. Teertstra; Christopher Phippen; Arthur F. J. Ram; Jens C. Frisvad; Han A. B. Wösten (Antonie van Leeuwenhoek, 2018)

Relative impacts of light, temperature, and reactive oxygen on thaumarchaeal ammonia oxidation in the North Pacific Ocean - Rachel E. A. Horak; Wei Qin; Anthony D. Bertagnolli; Alexa Nelson; Katherine R. Heal; Hantten Han; Maija Heller; Andrew J. Schauer; Wade H. Jeffrey; E. Virginia Armbrust; James W. Moffett; Anitra E. Ingalls; et al. (Limnology and Oceanography, 2018)
Thaumarchaeota are implicated as the major ammonia oxidizers in the ocean. However, the influence of various abiotic factors in determining their distribution and activity in the upper ocean remain largely unclear. Here, we examined the influence of light, hydrogen peroxide (H 2 O 2 ), and temperature on ammonia oxidation rates for communities dominated by Thaumarchaeota at the nitrite maximum across two North Pacific transects. In situ ammonia oxidation was almost exclusively driven by Thaumarchaeota , as inferred from ammonia monooxygenase subunit A ( amoA ) genes, amoA transcripts, and inhibitor studies. A major shift in population structure near the eastern North Pacific Subtropical Front was revealed by sequence variation of amoA genes, showing different Thaumarchaeota community structure in oligotrophic gyre and temperate regions. While the most dominant OTUs were closely related, we found significant differences in physiological responses to light and temperature of incubation. At four stations in different biogeochemical regimes, the impact of sunlight intensity and temperature on activity was evaluated using 15 ‐spiked whole seawater collected from the nitrite maximum and incubated at different depths on a free floating in situ array. Ammonia oxidation was usually completely inhibited by PAR at the surface and 21–45% inhibited at 1% surface PAR, whereas a temperature effect on ammonia oxidation was observed at only two of four stations. While inhibition due to H 2 O 2 cannot be ruled out in surface waters, our findings show that below the mixed layer, photoinhibition, and not H 2 O 2 toxicity, had a greater influence on ammonia oxidation.

Effects of Moisture-Induced Crystallization on the Aerosol Performance of Spray Dried Amorphous Ciprofloxacin Powder Formulations - Nivedita Shetty; Lingfei Zeng; Sharad Mangal; Haichen Nie; Matthew R. Rowles; Rui Guo; Youngwoo Han; Joon Hyeong Park; Qi Zhou (Pharmaceutical Research, 2018)

Signatures of polygenic adaptation associated with climate across the range of a threatened fish species with high genetic connectivity - Katherine A. Harrisson; Stephen J. Amish; Alexandra Pavlova; Shawn R. Narum; Marina Telonis‐Scott; Meaghan L. Rourke; Jarod Lyon; Zeb Tonkin; Dean M. Gilligan; Brett A. Ingram; Mark Lintermans; Han Ming Gan; et al. (Molecular Ecology, 2017)
Adaptive differences across species’ ranges can have important implications for population persistence and conservation management decisions. Despite advances in genomic technologies, detecting adaptive variation in natural populations remains challenging. Key challenges in gene–environment association studies involve distinguishing the effects of drift from those of selection and identifying subtle signatures of polygenic adaptation. We used paired‐end restriction site‐associated DNA sequencing data (6,605 biallelic single nucleotide polymorphisms; SNP s) to examine population structure and test for signatures of adaptation across the geographic range of an iconic Australian endemic freshwater fish species, the Murray cod Maccullochella peelii . Two univariate gene–association methods identified 61 genomic regions associated with climate variation. We also tested for subtle signatures of polygenic adaptation using a multivariate method (redundancy analysis; RDA ). The RDA analysis suggested that climate (temperature‐ and precipitation‐related variables) and geography had similar magnitudes of effect in shaping the distribution of SNP genotypes across the sampled range of Murray cod. Although there was poor agreement among the candidate SNP s identified by the univariate methods, the top 5% of SNP s contributing to significant RDA axes included 67% of the SNP s identified by univariate methods. We discuss the potential implications of our findings for the management of Murray cod and other species generally, particularly in relation to informing conservation actions such as translocations to improve evolutionary resilience of natural populations. Our results highlight the value of using a combination of different approaches, including polygenic methods, when testing for signatures of adaptation in landscape genomic studies.

Decreased plant productivity resulting from plant group removal experiment constrains soil microbial functional diversity - Ximei Zhang; Eric R. Johnston; Albert Barberán; Yi Ren; Xiaotao Lü; Xingguo Han (Global Change Biology, 2017)
Anthropogenic environmental changes are accelerating the rate of biodiversity loss on Earth. Plant diversity loss is predicted to reduce soil microbial diversity primarily due to the decreased variety of carbon/energy resources. However, this intuitive hypothesis is supported by sparse empirical evidence, and most underlying mechanisms remain underexplored or obscure altogether. We constructed four diversity gradients (0–3) in a five‐year plant functional group removal experiment in a steppe ecosystem in Inner Mongolia, China, and quantified microbial taxonomic and functional diversity with shotgun metagenome sequencing. The treatments had little effect on microbial taxonomic diversity, but were found to decrease functional gene diversity. However, the observed decrease in functional gene diversity was more attributable to a loss in plant productivity, rather than to the loss of any individual plant functional group per se. Reduced productivity limited fresh plant resources supplied to microorganisms, and thus, intensified the pressure of ecological filtering, favoring genes responsible for energy production/conversion, material transport/metabolism and amino acid recycling, and accordingly disfavored many genes with other functions. Furthermore, microbial respiration was correlated with the variation in functional composition but not taxonomic composition. Overall, the amount of carbon/energy resources driving microbial gene diversity was identified to be the critical linkage between above‐ and belowground communities, contrary to the traditional framework of linking plant clade/taxonomic diversity to microbial taxonomic diversity.

Study on the application of an activator for steel slag powder–cement in muddy soil - Y. K. Wu; X. S. Hu; R. Hu; T. Han; J. L. Yu (European Journal of Environmental and Civil Engineering, 2017)

Effect of Microneedle Type on Transdermal Permeation of Rizatriptan - Chandrateja Uppuluri; Ashraf Sultana Shaik; Tao Han; Atul Nayak; Karthik J. Nair; Benjamin R. Whiteside; Buchi N. Nalluri; Diganta B. Das (AAPS PharmSciTech, 2017)

The Contribution of Litterfall to Net Primary Production During Secondary Succession in the Boreal Forest - Han Y. H. Chen; Amber N. Brant; Meelis Seedre; Brian W. Brassard; Anthony R. Taylor (Ecosystems, 2017)

Global Mammal Parasite Database version 2.0 - Patrick R. Stephens; Paula Pappalardo; Shan Huang; James E. Byers; Maxwell J. Farrell; Alyssa Gehman; Ria R. Ghai; Sarah E. Haas; Barbara Han; Andrew W. Park; John P. Schmidt; Sonia Altizer; et al. (Ecology, 2017)
Illuminating the ecological and evolutionary dynamics of parasites is one of the most pressing issues facing modern science, and is critical for basic science, the global economy, and human health. Extremely important to this effort are data on the disease‐causing organisms of wild animal hosts (including viruses, bacteria, protozoa, helminths, arthropods, and fungi). Here we present an updated version of the Global Mammal Parasite Database, a database of the parasites of wild ungulates (artiodactyls and perissodactyls), carnivores, and primates, and make it available for download as complete flat files. The updated database has more than 24,000 entries in the main data file alone, representing data from over 2700 literature sources. We include data on sampling method and sample sizes when reported, as well as both “reported” and “corrected” (i.e., standardized) binomials for each host and parasite species. Also included are current higher taxonomies and data on transmission modes used by the majority of species of parasites in the database. In the associated metadata we describe the methods used to identify sources and extract data from the primary literature, how entries were checked for errors, methods used to georeference entries, and how host and parasite taxonomies were standardized across the database. We also provide definitions of the data fields in each of the four files that users can download.

Stand age affects emissions of N2O in flood-irrigated alfalfa: a comparison of field measurements, DNDC model simulations and IPCC Tier 1 estimates - Martin Burger; Van R. Haden; Han Chen; Johan Six; William R. Horwath (Nutrient Cycling in Agroecosystems, 2016)

Assessing the impacts of sea-level rise and precipitation change on the surficial aquifer in the low-lying coastal alluvial plains and barrier islands, east-central Florida (USA) - Han Xiao; Dingbao Wang; Scott C. Hagen; Stephen C. Medeiros; Carlton R. Hall (Hydrogeology Journal, 2016)

Evaluation of dynamically downscaled extreme temperature using a spatially-aggregated generalized extreme value (GEV) model - Jiali Wang; Yuefeng Han; Michael L. Stein; Veerabhadra R. Kotamarthi; Whitney K. Huang (Climate Dynamics, 2016)

The effects of petroleum-contaminated soil on photosynthesis of Amorpha fruticosa seedlings - G. Han; B. X. Cui; X. X. Zhang; K. R. Li (International Journal of Environmental Science and Technology, 2016)

Climate change‐associated trends in net biomass change are age dependent in western boreal forests of Canada - Han Y. H. Chen; Yong Luo; Peter B. Reich; Eric B. Searle; Shekhar R. Biswas (Ecology Letters, 2016)
The impacts of climate change on forest net biomass change are poorly understood but critical for predicting forest's contribution to the global carbon cycle. Recent studies show climate change‐associated net biomass declines in mature forest plots. The representativeness of these plots for regional forests, however, remains uncertain because we lack an assessment of whether climate change impacts differ with forest age. Using data from plots of varying ages from 17 to 210 years, monitored from 1958 to 2011 in western Canada, we found that climate change has little effect on net biomass change in forests ≤ 40 years of age due to increased growth offsetting increased mortality, but has led to large decreases in older forests due to increased mortality accompanying little growth gain. Our analysis highlights the need to incorporate forest age profiles in examining past and projecting future forest responses to climate change.

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Determinants of cancer screening in Asian-Americans - Quoc-Dien Trinh; Hanhan Li; Christian P. Meyer; Julian Hanske; Toni K. Choueiri; Gally Reznor; Stuart R. Lipsitz; Adam S. Kibel; Paul K. Han; Paul L. Nguyen; Mani Menon; Jesse D. Sammon (Cancer Causes & Control, 2016)

Comparison of helper component-protease RNA silencing suppression activity, subcellular localization, and aggregation of three Korean isolates of Turnip mosaic virus - Jae-Yeong Han; Jinsoo Chung; Jungkyu Kim; Eun-Young Seo; James P. Kilcrease; Gary R. Bauchan; Seungmo Lim; John Hammond; Hyoun-Sub Lim (Virus Genes, 2016)

Enhanced bioremoval of refractory compounds from dyeing wastewater using optimized sequential anaerobic/aerobic process - W. Bae; D. Han; E. Kim; R. A. de Toledo; K. Kwon; H. Shim (International Journal of Environmental Science and Technology, 2016)

Fine Mapping of qDor7, a Major QTL Affecting Seed Dormancy in Sorghum (Sorghum bicolor (L.) Moench) - Pan Li; Emma S. Mace; Yan Guo; Lijie Han; Mumu Wang; Yanfang He; Jun Chen; Nana Yuyama; David R. Jordan; Hongwei Cai (Tropical Plant Biology, 2016)

Introgression of genes from bread wheat enhances the aluminium tolerance of durum wheat - Chang Han; Peng Zhang; Peter R. Ryan; Tina M. Rathjen; ZeHong Yan; Emmanuel Delhaize (Theoretical and Applied Genetics, 2016)

Sand dunes as potential sources of dust in northern China - Mark R. Sweeney; HuaYu Lu; MengChun Cui; Joseph A. Mason; Han Feng; ZhiWei Xu (Science China Earth Sciences, 2016)

Aboveground biomass of understorey vegetation has a negligible or negative association with overstorey tree species diversity in natural forests - Yu Zhang; Han Y. H. Chen; Anthony R. Taylor (Global Ecology and Biogeography, 2016)
Aim The positive relationships between tree species diversity, aboveground biomass and productivity of overstorey tree layers have been widely reported in tropical, temperate and boreal forest ecosystems. However, no consensus has been arrived at on the association between overstorey tree species diversity and the functions of understorey vegetation, such as the biomass of understorey tree, shrub, herb and bryophyte layers, despite their critical contributions to the diversity and functions of natural forests. Location C anadian forest (42°37′ to 68°14′ N ; 53°25′ to 134°46′ W ; 4 to 2170 m elevation). Methods We employed C anada's N ational F orest I nventory dataset to evaluate the influences of overstorey tree species diversity on the aboveground biomass of each forest stratum by accounting for the effects of climate, site condition and stand age. Results We found that aboveground biomass of overstorey trees and total aboveground biomass were positively associated with overstorey tree species richness; however, the aboveground biomass of understorey trees, shrubs, herbs and bryophytes were not associated or were negatively associated with overstorey tree species richness, evenness and life‐history trait variations. Main conclusions Our results show positive associations between aboveground biomass of the overstorey tree layer and overstorey tree species diversity over a wide range of climate, local site conditions and stand ages in natural forests. However, contrary to previous findings that more tree species result in higher levels of multiple ecosystem functions, including understorey plant functions, our results demonstrate that the aboveground biomass of understorey vegetation has either a negligible or negative association with overstorey tree species diversity. The negative associations between overstorey tree species diversity and understorey biomass possibly resulted from greater resource filtering by overstorey trees in ecosystems with more diverse overstorey tree species.

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Trimeric autotransporter adhesins contribute to Actinobacillus pleuropneumoniae pathogenicity in mice and regulate bacterial gene expression during interactions between bacteria and porcine primary alveolar macrophages - Wanhai Qin; Lei Wang; Ruidong Zhai; Qiuyue Ma; Jianfang Liu; Chuntong Bao; Hu Zhang; Changjiang Sun; Xin Feng; Jingmin Gu; Chongtao Du; Wenyu Han; et al. (Antonie van Leeuwenhoek, 2016)

Environmental changes affect the assembly of soil bacterial community primarily by mediating stochastic processes - Ximei Zhang; Eric R. Johnston; Wei Liu; Linghao Li; Xingguo Han (Global Change Biology, 2016)
Both ‘species fitness difference’‐based deterministic processes, such as competitive exclusion and environmental filtering, and ‘species fitness difference’‐independent stochastic processes, such as birth/death and dispersal/colonization, can influence the assembly of soil microbial communities. However, how both types of processes are mediated by anthropogenic environmental changes has rarely been explored. Here we report a novel and general pattern that almost all anthropogenic environmental changes that took place in a grassland ecosystem affected soil bacterial community assembly primarily through promoting or restraining stochastic processes. We performed four experiments mimicking 16 types of environmental changes and separated the compositional variation of soil bacterial communities caused by each environmental change into deterministic and stochastic components, with a recently developed method. Briefly, because the difference between control and treatment communities is primarily caused by deterministic processes, the deterministic change was quantified as (mean compositional variation between treatment and control) – (mean compositional variation within control). The difference among replicate treatment communities is primarily caused by stochastic processes, so the stochastic change was estimated as (mean compositional variation within treatment) – (mean compositional variation within control). The absolute of the stochastic change was greater than that of the deterministic change across almost all environmental changes, which was robust for both taxonomic and functional‐based criterion. Although the deterministic change may become more important as environmental changes last longer, our findings showed that changes usually occurred through mediating stochastic processes over 5 years, challenging the traditional determinism‐dominated view.

Cognition and Depression Following Deep Brain Stimulation of the Subthalamic Nucleus and Globus Pallidus Pars Internus in Parkinson’s Disease: A Meta-Analysis - Hannah L. Combs; Bradley S. Folley; David T. R. Berry; Suzanne C. Segerstrom; Dong Y. Han; Amelia J. Anderson-Mooney; Brittany D. Walls; Craig van Horne (Neuropsychology Review, 2015)

Analysis of DDT and its metabolites in soil and water samples obtained in the vicinity of a closed-down factory in Bangladesh using various extraction methods - M. N. U. Al Mahmud; Farzana Khalil; Md. Musfiqur Rahman; M. I. R. Mamun; Mohammad Shoeb; A. M. Abd El-Aty; Jong-Hyouk Park; Ho-Chul Shin; Nilufar Nahar; Jae-Han Shim (Environmental Monitoring and Assessment, 2015)

A hybrid modelling approach for assessing solar radiation - M. A. Shamim; M. Bray; R. Remesan; D. Han (Theoretical and Applied Climatology, 2015)

Chlorella thermophila (Trebouxiophyceae, Chlorophyta), a novel thermo-tolerant Chlorella species isolated from an occupied rooftop incubator - Shuai Ma; Bingyin Han; Volker A. R. Huss; Xiaowen Hu; Xuepiao Sun; Jiaming Zhang (Hydrobiologia, 2015)

Rapid turnover of antimicrobial-type cysteine-rich protein genes in closely related Oryza genomes - Matthew R. Shenton; Hajime Ohyanagi; Zi-Xuan Wang; Atsushi Toyoda; Asao Fujiyama; Toshifumi Nagata; Qi Feng; Bin Han; Nori Kurata (Molecular Genetics and Genomics, 2015)

Fine mapping of qGW1, a major QTL for grain weight in sorghum - Lijie Han; Jun Chen; Emma S. Mace; Yishan Liu; Mengjiao Zhu; Nana Yuyama; David R. Jordan; Hongwei Cai (Theoretical and Applied Genetics, 2015)

Genetic polymorphism of APOB is associated with diabetes mellitus in sickle cell disease - Xu Zhang; Wei Zhang; Santosh L. Saraf; Mehdi Nouraie; Jin Han; Michel Gowhari; Johara Hassan; Galina Miasnikova; Adelina Sergueeva; Sergei Nekhai; Rick Kittles; Roberto F. Machado; et al. (Human Genetics, 2015)

Inhibiting β-Amyloid-Associated Alzheimer’s Pathogenesis In Vitro and In Vivo by a Multifunctional Dimeric Bis(12)-hupyridone Derived from Its Natural Analogue - Shengquan Hu; Rui Wang; Wei Cui; Zaijun Zhang; Shinghung Mak; Daping Xu; Chunglit Choi; Karl Wahkeung Tsim; Paul R. Carlier; Mingyuen Lee; Yifan Han (Journal of Molecular Neuroscience, 2015)

Social stress and escalated drug self-administration in mice II. Cocaine and dopamine in the nucleus accumbens - Xiao Han; Lucas Albrechet-Souza; Michelle R. Doyle; Akiko Shimamoto; Joseph F. DeBold; Klaus A. Miczek (Psychopharmacology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Effect of repeated exposures and sociality on novel food acceptance and consumption by orangutans - Madeleine E. Hardus; Adriano R. Lameira; Serge A. Wich; Han de Vries; Rachmad Wahyudi; Robert W. Shumaker; Steph B. J. Menken (Primates, 2015)

Intensification of decadal and multi-decadal sea level variability in the western tropical Pacific during recent decades - Weiqing Han; Gerald A. Meehl; Aixue Hu; Michael A. Alexander; Toshio Yamagata; Dongliang Yuan; Masayoshi Ishii; Philip Pegion; Jian Zheng; Benjamin D. Hamlington; Xiao-Wei Quan; Robert R. Leben (Climate Dynamics, 2014)

Recovery of Ecosystem Carbon Stocks in Young Boreal Forests: A Comparison of Harvesting and Wildfire Disturbance - Meelis Seedre; Anthony R. Taylor; Brian W. Brassard; Han Y. H. Chen; Kalev Jõgiste (Ecosystems, 2014)

Decline in Net Ecosystem Productivity Following Canopy Transition to Late-Succession Forests - Anthony R. Taylor; Meelis Seedre; Brian W. Brassard; Han Y. H. Chen (Ecosystems, 2014)

Adsorption of anionic dye on magnesium hydroxide-coated pyrolytic bio-char and reuse by microwave irradiation - X. N. Zhang; G. Y. Mao; Y. B. Jiao; Y. Shang; R. P. Han (International Journal of Environmental Science and Technology, 2014)

Effects of watershed land use on sources and nutritional value of particulate organic matter in temperate headwater streams - Yue Han Lu; Elizabeth A. Canuel; James E. Bauer; R. M. Chambers (Aquatic Sciences, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

The value of multiple earthquake missions: the EEFIT L’Aquila Earthquake experience - T. Rossetto; D. D’Ayala; F. Gori; R. Persio; J. Han; V. Novelli; S. M. Wilkinson; D. Alexander; M. Hill; S. Stephens; S. Kontoe; G. Elia; et al. (Bulletin of Earthquake Engineering, 2014)

CXCR4 pathway associated with family history of melanoma - Wen-Qing Li; Jiali Han; Hans R. Widlund; Mick Correll; Yaoyu E. Wang; John Quackenbush; Martin C. Mihm; Alvaro Laga Canales; Shaowei Wu; Todd Golub; Yujin Hoshida; David J. Hunter; et al. (Cancer Causes & Control, 2014)

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Comprehensive hormone profiling of the developing seeds of four grain legumes - Susan M. H. Slater; Hai Ying Yuan; Monika M. Lulsdorf; Albert Vandenberg; L. Irina Zaharia; Xiumei Han; Suzanne R. Abrams (Plant Cell Reports, 2013)

Genetic variations in the myostatin gene (MSTN) in New Zealand sheep breeds - J. Han; R. H. Forrest; J. G. H. Hickford (Molecular Biology Reports, 2013)

The C‐terminal cysteine of turbot Scophthalmus maximus translationally controlled tumour protein plays a key role in antioxidation and growth‐promoting functions - Z.‐X. Zhang; D.‐Y. Geng; Q. Han; S.‐D. Liang; H.‐R. Guo (Journal of Fish Biology, 2013)
The translationally controlled tumour protein (TCTP) of turbot Scophthalmus maximus ( SmTCTP ) contains only one cysteine (Cys 170 ) at the C‐terminal end. The biological role of this C‐terminal Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP was examined by site‐directed mutation of C170A (Cys 170 →Ala 170 ). It was found that C170A mutation not only obviously decreased the antioxidation capacity of the mutant‐ smtctp ‐transformed bacteria exposed to 0·22 mM hydrogen peroxide, but also significantly interrupted the normal growth and survival of the mutant‐ smtctp ‐transformed bacteria and flounder Paralichthys olivaceus gill ( FG ) cells, indicating a key role played by Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP . This study also suggested that the self‐dimerization or dimerization with other interacting proteins is critical to the growth‐promoting function of SmTCTP .

More breast cancer patients prefer BRCA-mutation testing without prior face-to-face genetic counseling - Aisha S. Sie; Wendy A. G. van Zelst-Stams; Liesbeth Spruijt; Arjen R. Mensenkamp; Marjolijn J. L. Ligtenberg; Han G. Brunner; Judith B. Prins; Nicoline Hoogerbrugge (Familial Cancer, 2013)

Characterization of the root-predominant gene promoter HPX1 in transgenic rice plants - Su-Hyun Park; Jin Seo Jeong; Eun Hyang Han; Mark C. F. R. Redillas; Seung Woon Bang; Harin Jung; Youn Shic Kim; Ju-Kon Kim (Plant Biotechnology Reports, 2013)

Artery Buckling: New Phenotypes, Models, and Applications - Hai-Chao Han; Jennifer K. W. Chesnutt; Justin R. Garcia; Qin Liu; Qi Wen (Annals of Biomedical Engineering, 2013)

Erratum to: Regulation of Phytohormone Biosynthesis and Accumulation in Arabidopsis Following Treatment with Commercial Extract from the Marine Macroalga Ascophyllum nodosum - Owen S. D. Wally; Alan T. Critchley; David Hiltz; James S. Craigie; Xiumei Han; L. Irina Zaharia; Suzanne R. Abrams; Balakrishnan Prithiviraj (Journal of Plant Growth Regulation, 2013)

Regulation of Phytohormone Biosynthesis and Accumulation in Arabidopsis Following Treatment with Commercial Extract from the Marine Macroalga Ascophyllum nodosum - Owen S. D. Wally; Alan T. Critchley; David Hiltz; James S. Craigie; Xiumei Han; L. Irina Zaharia; Suzanne R. Abrams; Balakrishnan Prithiviraj (Journal of Plant Growth Regulation, 2013)

Quantification of TRPV1 Protein Levels in Rat Tissues to Understand its Physiological Roles - Ping Han; Alla V. Korepanova; Melissa H. Vos; Robert B. Moreland; Mark L. Chiu; Connie R. Faltynek (Journal of Molecular Neuroscience, 2013)

Ordered subset linkage analysis based on admixture proportion identifies new linkage evidence for alcohol dependence in African-Americans - Shizhong Han; Joel Gelernter; Henry R. Kranzler; Bao-Zhu Yang (Human Genetics, 2013)

Clustering of place of birth for women with breast cancer: differences by tumor characteristics - Daikwon Han; Jing Nie; Matthew R. Bonner; Christine Ambrosone; Catalin Marian; Peter Shields; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2013)

Predator guild does not influence orangutan alarm call rates and combinations - Adriano R. Lameira; Han de Vries; Madeleine E. Hardus; Cedric P. A. Hall; Tatang Mitra-Setia; Berry M. Spruijt; Arik Kershenbaum; Elisabeth H. M. Sterck; Maria van Noordwijk; Carel van Schaik; Serge A. Wich (Behavioral Ecology and Sociobiology, 2013)

Socioecological correlates of inter-individual variation in orangutan diets at Ketambe, Sumatra - Madeleine E. Hardus; Han de Vries; David F. Dellatore; Adriano R. Lameira; Steph B. J. Menken; Serge A. Wich (Behavioral Ecology and Sociobiology, 2013)

Effect of initial biomass density on growth and astaxanthin production of Haematococcus pluvialis in an outdoor photobioreactor - Junfeng Wang; Danxiang Han; Milton R. Sommerfeld; Congming Lu; Qiang Hu (Journal of Applied Phycology, 2013)

Desulfohalophilus alkaliarsenatis gen. nov., sp. nov., an extremely halophilic sulfate- and arsenate-respiring bacterium from Searles Lake, California - Jodi Switzer Blum; Thomas R. Kulp; Sukkyun Han; Brian Lanoil; Chad W. Saltikov; John F. Stolz; Laurence G. Miller; Ronald S. Oremland (Extremophiles, 2012)

Climate oscillation during the Quaternary associated with landscape heterogeneity promoted allopatric lineage divergence of a temperate tree Kalopanax septemlobus (Araliaceae) in East Asia - SHOTA SAKAGUCHI; YING‐XIONG QIU; YI‐HUI LIU; XIN‐SHUAI QI; SEA‐HYUN KIM; JINGYU HAN; YAYOI TAKEUCHI; JAMES R. P. WORTH; MICHIMASA YAMASAKI; SHOGO SAKURAI; YUJI ISAGI (Molecular Ecology, 2012)
We investigated the biogeographic history of Kalopanax septemlobus , one of the most widespread temperate tree species in East Asia, using a combined phylogeographic and palaeodistribution modelling approach. Range‐wide genetic differentiation at nuclear microsatellites ( G ′ ST = 0.709; 2205 samples genotyped at five loci) and chloroplast DNA ( G ST = 0.697; 576 samples sequenced for 2055 bp at three fragments) was high. A major phylogeographic break in Central China corresponded with those of other temperate species and the spatial delineation of the two temperate forest subkingdoms of East Asia, consistent with the forests having been isolated within both East and West China for multiple glacial–interglacial cycles. Evidence for multiple glacial refugia was found in most of its current range in China, South Japan and the southernmost part of the Korean Peninsula. In contrast, lineage admixture and absence of private alleles and haplotypes in Hokkaido and the northern Korean Peninsula support a postglacial origin of northernmost populations. Although palaeodistribution modelling predicted suitable climate across a land‐bridge extending from South Japan to East China during the Last Glacial Maximum, the genetic differentiation of regional populations indicated a limited role of the exposed sea floor as a dispersal corridor at that time. Overall, this study provides evidence that differential impacts of Quaternary climate oscillation associated with landscape heterogeneity have shaped the genetic structure of a wide‐ranging temperate tree in East Asia.

Effect of elevated carbon dioxide on growth and nitrogen fixation of two soybean cultivars in northern China - Shu Kee Lam; Xingyu Hao; Erda Lin; Xue Han; Rob Norton; Arvin R. Mosier; Saman Seneweera; Deli Chen (Biology and Fertility of Soils, 2012)

Total centromere size and genome size are strongly correlated in ten grass species - Han Zhang; R. Kelly Dawe (Chromosome Research, 2012)

Behavioral, Ecological, and Evolutionary Aspects of Meat-Eating by Sumatran Orangutans (Pongo abelii) - Madeleine E. Hardus; Adriano R. Lameira; Astri Zulfa; S. Suci Utami Atmoko; Han de Vries; Serge A. Wich (International Journal of Primatology, 2012)

A test of ecological succession hypotheses using 55‐year time‐series data for 361 boreal forest stands - Han Y. H. Chen; Anthony R. Taylor (Global Ecology and Biogeography, 2012)
Aim There has been much work on succession over many decades, but succession fundamentals are still debated because of the reliance on chronosequences and dendrochronological reconstruction, both of which are problematic approaches. Here we use time‐series data to test four hypotheses that lie at the heart of successional theory: (1) the neighbourhood effect hypothesis – tree species abundance is time dependent; (2) the density‐dependence hypothesis – a rare species is more favoured over time; (3) the resource ratio hypothesis – species that can grow at the lowest resource level tend to dominate resource limited sites through succession; and (4) the intermediate disturbance hypothesis – intermediate disturbances increase the abundance of rare species. Location Central boreal forest in Canada (47°50′–50°10′ N; 80°10′–85°50′ W). Methods We used repeated measurements from sequential aerial photography and ground surveys for 361 fire‐origin stands that were measured over a c . 55‐year period. Results Shade‐intolerant Pinus banksiana decreased, tolerant Thuja occidentalis increased, intolerant Populus spp. and Betula papyrifera displayed a U‐shaped trend, and intermediate‐tolerant Picea spp. and tolerant Abies balsamea did not change with time since fire, showing evidence of negative, positive, or neutral neighbourhood effects. Species either persisted for longer or increased more in non‐conspecific stands, and had higher increases in abundance when associated with species of contrasting shade tolerance, supporting the density‐dependence hypothesis and indicating shade‐tolerance complementarity as a mechanism for coexistence. Resource‐poor soils favoured those species capable of tolerating limited resources, whereas rich soils permitted invasion and promoted mixtures, supporting the resource ratio hypothesis. Intermediate disturbances increased the invasibility of rare species. Main conclusions Contrary to previous studies where time since a stand‐replacing disturbance is the sole predictor for succession, our study shows that time alone is either an insufficient predictor or is irrelevant to species dynamics in the boreal forest. Rather, density dependence, site resource and intermediate disturbances are key mechanisms in species dynamics and coexistence over time.

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Specimen‐Based Modeling, Stopping Rules, and the Extinction of the Ivory‐Billed Woodpecker - NICHOLAS J. GOTELLI; ANNE CHAO; ROBERT K. COLWELL; WEN‐HAN HWANG; GARY R. GRAVES (Conservation Biology, 2012)
Assessing species survival status is an essential component of conservation programs. We devised a new statistical method for estimating the probability of species persistence from the temporal sequence of collection dates of museum specimens. To complement this approach, we developed quantitative stopping rules for terminating the search for missing or allegedly extinct species. These stopping rules are based on survey data for counts of co‐occurring species that are encountered in the search for a target species. We illustrate both these methods with a case study of the Ivory‐billed Woodpecker ( Campephilus principalis ), long assumed to have become extinct in the United States in the 1950s, but reportedly rediscovered in 2004. We analyzed the temporal pattern of the collection dates of 239 geo‐referenced museum specimens collected throughout the southeastern United States from 1853 to 1932 and estimated the probability of persistence in 2011 as −5 , with a probable extinction date no later than 1980. From an analysis of avian census data (counts of individuals) at 4 sites where searches for the woodpecker were conducted since 2004, we estimated that at most 1–3 undetected species may remain in 3 sites (one each in Louisiana, Mississippi, Florida). At a fourth site on the Congaree River (South Carolina), no singletons (species represented by one observation) remained after 15,500 counts of individual birds, indicating that the number of species already recorded (56) is unlikely to increase with additional survey effort. Collectively, these results suggest there is virtually no chance the Ivory‐billed Woodpecker is currently extant within its historical range in the southeastern United States. The results also suggest conservation resources devoted to its rediscovery and recovery could be better allocated to other species. The methods we describe for estimating species extinction dates and the probability of persistence are generally applicable to other species for which sufficient museum collections and field census results are available.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

A High Arctic soil ecosystem resists long‐term environmental manipulations - ERIC G. LAMB; SUKKYUN HAN; BRIAN D. LANOIL; GREG H. R. HENRY; MARTIN E. BRUMMELL; SAMIRAN BANERJEE; STEVEN D. SICILIANO (Global Change Biology, 2011)
We evaluated above‐ and belowground ecosystem changes in a 16 year, combined fertilization and warming experiment in a High Arctic tundra deciduous shrub heath (Alexandra Fiord, Ellesmere Island, NU, Canada). Soil emissions of the three key greenhouse gases (GHGs) (carbon dioxide, methane, and nitrous oxide) were measured in mid‐July 2009 using soil respiration chambers attached to a FTIR system. Soil chemical and biochemical properties including Q 10 values for CO 2 , CH 4 , and N 2 O, Bacteria and Archaea assemblage composition, and the diversity and prevalence of key nitrogen cycling genes including bacterial amoA , crenarchaeal amoA , and nosZ were measured. Warming and fertilization caused strong increases in plant community cover and height but had limited effects on GHG fluxes and no substantial effect on soil chemistry or biochemistry. Similarly, there was a surprising lack of directional shifts in the soil microbial community as a whole or any change at all in microbial functional groups associated with CH 4 consumption or N 2 O cycling in any treatment. Thus, it appears that while warming and increased nutrient availability have strongly affected the plant community over the last 16 years, the belowground ecosystem has not yet responded. This resistance of the soil ecosystem has resulted in limited changes in GHG fluxes in response to the experimental treatments.

Individual and combined effects of multiple pathogens on Pacific treefrogs - John M. Romansic; Pieter T. J. Johnson; Catherine L. Searle; James E. Johnson; Tate S. Tunstall; Barbara A. Han; Jason R. Rohr; Andrew R. Blaustein (Oecologia, 2011)

Species-level correlates of susceptibility to the pathogenic amphibian fungus Batrachochytrium dendrobatidis in the United States - Betsy A. Bancroft; Barbara A. Han; Catherine L. Searle; Lindsay M. Biga; Deanna H. Olson; Lee B. Kats; Joshua J. Lawler; Andrew R. Blaustein (Biodiversity and Conservation, 2011)

Absence of repellents in Ustilago maydis induces genes encoding small secreted proteins - Wieke R. Teertstra; Pauline Krijgsheld; Han A. B. Wösten (Antonie van Leeuwenhoek, 2011)

The spatial and temporal subsidence variability of the East Mesa Geothermal Field, California, USA, and its potential impact on the All American Canal System - Joo-Yup Han; R. R. Forster; D. E. Moser; A. L. J. Ford; J. Ramírez-Hernández; K. F. Tiampo (International Journal of Remote Sensing, 2011)

The physico-chemical characterization of casein-modified surfaces and their influence on the adhesion of spores from a Geobacillus species - Jingtian Han; R Brent Seale; Patrick Silcock; A James McQuillan; Phil J. Bremer (Biofouling, 2011)

Mechanisms of plant spindle formation - Han Zhang; R. Kelly Dawe (Chromosome Research, 2011)

Human Cannabinoid 1 GPCR C-Terminal Domain Interacts with Bilayer Phospholipids to Modulate the Structure of its Membrane Environment - Elvis K. Tiburu; Sergiy Tyukhtenko; Han Zhou; David R. Janero; Jochem Struppe; Alexandros Makriyannis (The AAPS Journal, 2011)

The genome of the Gram‐positive metal‐ and sulfate‐reducing bacterium Desulfotomaculum reducens strain MI‐1 - Pilar Junier; Thomas Junier; Sheila Podell; David R. Sims; John C. Detter; Athanasios Lykidis; Cliff S. Han; Nicholas S. Wigginton; Terry Gaasterland; Rizlan Bernier‐Latmani (Environmental Microbiology, 2010)
Summary Spore‐forming, Gram‐positive sulfate‐reducing bacteria (SRB) represent a group of SRB that dominates the deep subsurface as well as niches in which resistance to oxygen and dessication is an advantage. Desulfotomaculum reducens strain MI‐1 is one of the few cultured representatives of that group with a complete genome sequence available. The metabolic versatility of this organism is reflected in the presence of genes encoding for the oxidation of various electron donors, including three‐ and four‐carbon fatty acids and alcohols. Synteny in genes involved in sulfate reduction across all four sequenced Gram‐positive SRB suggests a distinct sulfate‐reduction mechanism for this group of bacteria. Based on the genomic information obtained for sulfate reduction in D. reducens , the transfer of electrons to the sulfite and APS reductases is proposed to take place via the quinone pool and heterodisulfide reductases respectively. In addition, both H 2 ‐evolving and H 2 ‐consuming cytoplasmic hydrogenases were identified in the genome, pointing to potential cytoplasmic H 2 cycling in the bacterium. The mechanism of metal reduction remains unknown.

OsPRA1 plays a significant role in targeting of OsRab7 into the tonoplast via the prevacuolar compartment during vacuolar trafficking in plant cells - Jae Bok Heo; Woo Young Bang; Se Won Kim; Sung Min Hwang; Young Sim Son; Chak Han Im; Biswa R. Acharya; Chul Wook Kim; Sam Woong Kim; Byung Hyun Lee; Jeong Dong Bahk (Planta, 2010)

The genome of Syntrophomonas wolfei : new insights into syntrophic metabolism and biohydrogen production - Jessica R. Sieber; David R. Sims; Cliff Han; Edwin Kim; Athanasios Lykidis; Alla L. Lapidus; Erin McDonnald; Lars Rohlin; David E. Culley; Robert Gunsalus; Michael J. McInerney (Environmental Microbiology, 2010)
Summary Syntrophomonas wolfei is a specialist, evolutionarily adapted for syntrophic growth with methanogens and other hydrogen‐ and/or formate‐using microorganisms. This slow‐growing anaerobe has three putative ribosome RNA operons, each of which has 16S rRNA and 23S rRNA genes of different length and multiple 5S rRNA genes. The genome also contains 10 RNA‐directed, DNA polymerase genes. Genomic analysis shows that S. wolfei relies solely on the reduction of protons, bicarbonate or unsaturated fatty acids to re‐oxidize reduced cofactors. Syntrophomonas wolfei lacks the genes needed for aerobic or anaerobic respiration and has an exceptionally limited ability to create ion gradients. An ATP synthase and a pyrophosphatase were the only systems detected capable of creating an ion gradient. Multiple homologues for β‐oxidation genes were present even though S. wolfei uses a limited range of fatty acids from four to eight carbons in length . Syntrophomonas wolfei , other syntrophic metabolizers with completed genomic sequences, and thermophilic anaerobes known to produce high molar ratios of hydrogen from glucose have genes to produce H 2 from NADH by an electron bifurcation mechanism. Comparative genomic analysis also suggests that formate production from NADH may involve electron bifurcation. A membrane‐bound, iron–sulfur oxidoreductase found in S. wolfei and Syntrophus aciditrophicus may be uniquely involved in reverse electron transport during syntrophic fatty acid metabolism. The genome sequence of S. wolfei reveals several core reactions that may be characteristic of syntrophic fatty acid metabolism and illustrates how biological systems produce hydrogen from thermodynamically difficult reactions.

Effect of paraquat on the antioxidative enzyme activities and lipid peroxidation in opium poppy (Papaver somniferum L.) - R. Zhao; P. -Y. Guo; X. -Y. Yuan; J. -Y. Wang; M. -Q. Han (Journal of Plant Diseases and Protection, 2010)

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Experimental examination of the effects of ultraviolet-B radiation in combination with other stressors on frog larvae - Catherine Laura Searle; Lisa K. Belden; Betsy A. Bancroft; Barbara A. Han; Lindsay M. Biga; Andrew R. Blaustein (Oecologia, 2010)

Jasmine tea consumption and upper gastrointestinal cancer in China - Ying Gao; Nan Hu; XiaoYou Han; Carol Giffen; Ti Ding; Alisa M. Goldstein; Philip R. Taylor (Cancer Causes & Control, 2009)

Prothoracic Gland Semiochemicals of Green Lacewings - Jeffrey Richard Aldrich; Thanh C. Le; Qing-He Zhang; Jorge Torres; Shaun L. Winterton; Baoyu Han; Gary L. Miller; Kamlesh R. Chauhan (Journal of Chemical Ecology, 2009)

Embryogenic tissue initiation and somatic embryogenesis in Fraser fir (Abies fraseir [Pursh] Poir.) - Y. W. Kim; R. Newton; J. Frampton; K.-H. Han (In Vitro Cellular & Developmental Biology - Plant, 2009)

International patterns and trends in thyroid cancer incidence, 1973–2002 - Briseis A. Kilfoy; Tongzhang Zheng; Theodore R. Holford; Xuesong Han; Mary H. Ward; Andreas Sjodin; Yaqun Zhang; Yana Bai; Cairong Zhu; Grace L. Guo; Nathaniel Rothman; Yawei Zhang (Cancer Causes & Control, 2009)

A Review of Forest Succession Models and Their Suitability for Forest Management Planning - Anthony R. Taylor; Han Y. H. Chen; Laird VanDamme (Forest Science, 2009)
Successful implementation of ecosystem management requires strategic forest management planning, including the ability to forecast future forest composition. With advances in ecological modeling, many forms of succession models are available. In this review, we provide a broad synthesis of the methods used to model forest succession and discuss their suitability for strategic forest management planning. Qualitative models underpin theoretical understanding of forest succession but require expression in more formal quantitative forms to be applicable to strategic planning. Quantitative modeling methods can be differentiated as empirical or mechanistic. Empirical models rely on observational data of successional change. Mechanistic models rely on knowledge of underlying ecological processes to simulate succession. Hybrid mechanistic models represent a compromise in ecological modeling between empirical robustness and theoretical understanding. With their increased flexibility for scenario planning and enhanced representation of ecosystem processes, hybrid models are well suited to addressing the multiple environmental and social factors increasingly being considered under ecosystem management. However, empirical models still remain a suitable and practical alternative because hybrid models require increased resources to initialize, operate, and interpret; emphasize understanding rather than prediction; and assume that the modeled processes they represent are adequately understood.

Polyplex Micelles from Triblock Copolymers Composed of Tandemly Aligned Segments with Biocompatible, Endosomal Escaping, and DNA-Condensing Functions for Systemic Gene Delivery to Pancreatic Tumor Tissue - Kanjiro Miyata; Makoto Oba; Mitsunobu R. Kano; Shigeto Fukushima; Yelena Vachutinsky; Muri Han; Hiroyuki Koyama; Kohei Miyazono; Nobuhiro Nishiyama; Kazunori Kataoka (Pharmaceutical Research, 2008)

Ancient behaviors of larval amphibians in response to an emerging fungal pathogen, Batrachochytrium dendrobatidis - Barbara A. Han; Paul W. Bradley; Andrew R. Blaustein (Behavioral Ecology and Sociobiology, 2008)

Lymphoma survival patterns by WHO subtype in the United States, 1973–2003 - Xuesong Han; Briseis Kilfoy; Tongzhang Zheng; Theodore R. Holford; Cairong Zhu; Yong Zhu; Yawei Zhang (Cancer Causes & Control, 2008)

Characterization and comparison of intron structure and alternative splicing between Medicago truncatula, Populus trichocarpa, Arabidopsis and rice - Jong-Min Baek; Paul Han; Alberto Iandolino; Douglas R. Cook (Plant Molecular Biology, 2008)

Effects of brassinolide on the survival, growth and drought resistance of Robinia pseudoacacia seedlings under water-stress - K. R. Li; H. H. Wang; G. Han; Q. J. Wang; J. Fan (New Forests, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Characterization of a Homogentisate Dioxygenase Mutant in Pseudomonas chlororaphis O6 - B. R. Kang; S. H. Han; S. M. Cho; A. J. Anderson; I. S. Kim; S. K. Park; Y. C. Kim (Current Microbiology, 2008)

Effect of a Hydrophobic Phospholipid Lining of the Gastric Mucosa in Bioadhesion - Jae Han Park; Joseph R. Robinson (Pharmaceutical Research, 2008)

Exposure to traffic emissions throughout life and risk of breast cancer: the Western New York Exposures and Breast Cancer (WEB) study - Jing Nie; Jan Beyea; Matthew R. Bonner; Daikwon Han; John E. Vena; Peter Rogerson; Dominica Vito; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2007)

A novel gene, Pi40(t), linked to the DNA markers derived from NBS-LRR motifs confers broad spectrum of blast resistance in rice - J. U. Jeung; B. R. Kim; Y. C. Cho; S. S. Han; H. P. Moon; Y. T. Lee; K. K. Jena (Theoretical and Applied Genetics, 2007)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effect of Cadmium in Feed on Organs and Meat Colour of Growing Pigs - Y.-J. Tu; X.-Y. Han; Z.-R. Xu; Y.-Z. Wang; W.-F. Li (Veterinary Research Communications, 2007)

Direct evidence that two cysteines in the dopamine transporter form a disulfide bond - Rong Chen; Hua Wei; Erik R. Hill; Lucy Chen; Liying Jiang; Dawn D. Han; Howard H. Gu (Molecular and Cellular Biochemistry, 2007)

Approaching chickpea quantitative trait loci conditioning resistance to Ascochyta rabiei via comparative genomics - X. Y. Bian; R. Ford; T. R. Han; T. E. Coram; E. C. K. Pang; P. W. J. Taylor (Australasian Plant Pathology, 2007)

Volume density and distribution of mitochondria in harbor seal (Phoca vitulina) skeletal muscle - Rebecca R. Watson; Shane B. Kanatous; Daniel F. Cowan; Julie W. Wen; Violet C. Han; Randall W. Davis (Journal of Comparative Physiology B, 2006)

Intratumoral cytokines/chemokines/growth factors and tumor infiltrating dendritic cells: friends or enemies? - Michael R. Shurin; Galina V. Shurin; Anna Lokshin; Zoya R. Yurkovetsky; Dmitry W. Gutkin; Gurkamal Chatta; Hua Zhong; Baohui Han; Robert L. Ferris (Cancer and Metastasis Reviews, 2006)

Tests of Models for Saccade–Vergence Interaction using Novel Stimulus Conditions - Arun N. Kumar; Yanning H. Han; Robert F. Kirsch; Louis F. Dell’Osso; W. Michael King; R. John Leigh (Biological Cybernetics, 2006)

Post-harvest Regeneration of Lowland Black Spruce Forests in Northeastern Ontario - Han Y. H. Chen; Jian R. Wang (New Forests, 2006)

Fibroblast migration after myocardial infarction is regulated by transient SPARC expression - Rong Xue Wu; Martin Laser; Hong Han; Jeeva Varadarajulu; Kai Schuh; Matthias Hallhuber; Kai Hu; Georg Ertl; Christof R. Hauck; Oliver Ritter (Journal of Molecular Medicine, 2006)

Meprin β metalloprotease gene polymorphisms associated with diabetic nephropathy in the Pima Indians - Alexander R. Red Eagle; Robert L. Hanson; Weiping Jiang; Xiaoli Han; Gail L. Matters; Giuseppina Imperatore; William C. Knowler; Judith S. Bond (Human Genetics, 2005)

Interspecific Variation in Susceptibility of Frog Tadpoles to the Pathogenic Fungus Batrachochytrium dendrobatidis - ANDREW R. BLAUSTEIN; JOHN M. ROMANSIC; ERIN A. SCHEESSELE; BARBARA A. HAN; ALLAN P. PESSIER; JOYCE E. LONGCORE (Conservation Biology, 2005)
As part of an overall biodiversity crisis many amphibian populations are in decline throughout the world. Numerous causes have been invoked to explain these declines. These include habitat destruction, climate change, increasing levels of ultraviolet radiation, environmental contamination, and the introduction of non‐native species and diseases. Several types of pathogens have been implicated in contributing to amphibian population declines: viruses, bacteria, oomycetes, and fungi. One particular fungus, the chytridiomycete Batrachochytrium dendrobatidis may have caused amphibian population declines in several regions. This pathogen causes chytridiomycosis, which is fatal to newly metamorphic and adult amphibians of certain species. We present experimental evidence that larval stages may also be susceptible to exposure to Batrachochytrium . There was, however, differential sensitivity to B. dendrobatidis in larvae we examined. In laboratory experiments, larval western toads ( Bufo boreas ) exposed to B. dendrobatidis experienced increased mortality and behaviors that suggested they were affected by exposure compared with unexposed control tadpoles. Larvae of Cascades frogs ( Rana cascadae ), bullfrogs ( R. catesbeiana ), and Pacific treefrogs ( Hyla regilla ) did not die after exposure to Batrachochytrium and appeared to behave normally. R. cascadae larvae exposed to B. dendrobatidis , however, showed an increase incidence in mouthpart abnormalities, a characteristic effect of chytridiomycosis, compared with unexposed controls. These results show that Batrachochytrium can negatively affect some species of amphibians at the larval stage and not others. The implications of interspecific variation in susceptibility to fungal infection are broad.

Vestibular and non-vestibular contributions to eye movements that compensate for head rotations during viewing of near targets - Yanning H. Han; Arun N. Kumar; Millard F. Reschke; Jeffrey T. Somers; Louis F. Dell’Osso; R. John. Leigh (Experimental Brain Research, 2005)

Secondhand smoke exposure in early life and the risk of breast cancer among never smokers (United States) - Matthew R. Bonner; Jing Nie; Daikwon Han; John E. Vena; Peter Rogerson; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2005)

Molecular analysis of congenital scoliosis: a candidate gene approach - Melissa K. Maisenbacher; Ji-Soo Han; Megan L. O’Brien; Michael R. Tracy; Bülent Erol; Alyssa A. Schaffer; John P. Dormans; Elaine H. Zackai; Kenro Kusumi (Human Genetics, 2005)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Geographic clustering of residence in early life and subsequent risk of breast cancer (United States) - Daikwon Han; Peter A. Rogerson; Jing Nie; Matthew R. Bonner; John E. Vena; Dominica Vito; Paola Muti; Maurizio Trevisan; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Thermostable Alkaline Protease from a Novel Marine Haloalkalophilic Bacillus Clausii Isolate - C. Ganesh Kumar; Han-Seung Joo; Yoon-Mo Koo; Seung R. Paik; Chung-Soon Chang (World Journal of Microbiology and Biotechnology, 2004)

Block Estimating of Spatial Yield Data and its Uncertainty - Shufeng Han; Sally M. Schneider; Robert G. Evans; Joan R. Davenport (Precision Agriculture, 2004)

Novel types of mutation in the choroideremia (CHM) gene: a full-length L1 insertion and an intronic mutation activating a cryptic exon - José A. J. M. van den Hurk; Dorien J. R. van de Pol; Bernd Wissinger; Marc A. van Driel; Lies H. Hoefsloot; Ilse J. de Wijs; L. Ingeborgh van den Born; John R. Heckenlively; Han G. Brunner; Eberhart Zrenner; Hans-Hilger Ropers; Frans P. M. Cremers (Human Genetics, 2003)

Recognition and implication of tectonic loading-induced reheating in the northern Variscan front (Belgium and northern France), based on an illite Kbler index and oxygen isotope study - G. Han; J. Yans; M. Goudalier; F. Lacquement; R. M. Corfield; J. L. Mansy; F. Boulvain; A. Prat (International Journal of Earth Sciences, 2003)

Characterization of genotype II Rubella virus strains - D.-P. Zheng; Y. M. Zhou; K. Zhao; Y.-R. Han; T. K. Frey (Archives of Virology, 2003)

PermophricodothyrisPavlova, 1965 (Brachiopoda, Spiriferida) from the Permian of South China: its morphology, biostratigraphy and distribution - Guang R. Shi; Zhong-Qiang Chen; Nai-Ren Han (PalZ, 2002)

Differential distribution of interneurons in the neural networks that control walking in the mudpuppy (Necturus maculatus) spinal cord - J. Cheng; K. Jovanovic; Y. Aoyagi; D. J. Bennett; Y. Han; R. B. Stein (Experimental Brain Research, 2002)

Workshop on Bioanalytical Methods Validation for Macromolecules: Summary Report - Krys J. Miller; Ronald R. Bowsher; Abbie Celniker; Jacqueline Gibbons; Shalini Gupta; Jean W. Lee; Steve J. Swanson; Wendell C. Smith; Russell S. Weiner; Daan J. A. Crommelin; Ira Das; Binodh S. DeSilva; et al. (Pharmaceutical Research, 2001)

Physical and Chemical Properties of a Winter-Time Yellow Sand Event in Northeast Asia - B. G. Kim; J. Y. Ahn; H. R. Noh; C. J. Park; J. S. Han; S. U. Park (Water, Air, & Soil Pollution, 2001)

Hydroxyproline-rich glycoproteins expressed during stress responses in cassava - Yuanhuai Han; Rocío Gómez-Vásquez; Kim Reilly; Hongying Li; Joe Tohme; Richard M. Cooper; John R. Beeching (Euphytica, 2001)

Molecular mapping of a new gene for resistance to rice blast (Pyricularia grisea Sacc.) - Sang-Nag Ahn; Yeon-Kyu Kim; Ha-Cheol Hong; Seong-Sook Han; Soo-Jin Kwon; Hae-Chune Choi; Huhn-Pal Moon; Susan R. McCouch (Euphytica, 2000)

Physical mapping of the barley stem rust resistance gene rpg4 - A. Druka; D. Kudrna; F. Han; A. Kilian; B. Steffenson; D. Frisch; J. Tomkins; R. Wing; A. Kleinhofs (Molecular Genetics and Genomics, 2000)

Angiotensin II induces gene transcription through cell-type-dependent effects on the nuclear factor-κB (NF-κB) transcription factor - Allan R. Brasier; M. Jamaluddin; Youqui Han; Cam Patterson; Marschall S. Runge (Molecular and Cellular Biochemistry, 2000)

An integrated genetic map of Populus deltoides based on amplified fragment length polymorphisms - R. L. Wu; Y. F. Han; J. J. Hu; J. J. Fang; L. Li; M. L. Li; Z. -B. Zeng (Theoretical and Applied Genetics, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Host effect on genetic variation of Marssonina brunnea pathogenic to poplars - Z. M. Han; T. M. Yin; C. D. Li; M. R. Huang; R.L. Wu (Theoretical and Applied Genetics, 2000)

An Agrobacterium tumefaciens transformation protocol effective on a variety of cottonwood hybrids (genus Populus ) - K.-H. Han; R. Meilan; C. Ma; S. H. Strauss (Plant Cell Reports, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Detection and quantitation of a sodium-dependent sulfate cotransporter (NaSi-1) by sandwich-type enzyme-linked immunosorbent assay - Kazuko Sagawa; Debra C. DuBois; Bing Han; Richard R. Almon; Jürg Biber; Heini Murer; M. E. Morris (Pflügers Archiv - European Journal of Physiology, 1998)

Estimation of Target Hazard Quotients and Potential Health Risks for Metals by Consumption of Seafood in Taiwan - B.-C. Han; W. L. Jeng; R. Y. Chen; G. T. Fang; T. C. Hung; R. J. Tseng (Archives of Environmental Contamination and Toxicology, 1998)

The longitudinal development of running economy in males and females aged between 13 and 27 years: The Amsterdam Growth and Health Study - Geertje A. M. Arins; Willem van Mechelen; Han C. G. Kemper; Jos W. R. Twisk; Willem van Mechelen (European Journal of Applied Physiology, 1997)

Changes in late-embryogenesis-abundant (LEA) messenger RNAs and dehydrins during maturation and premature drying ofRicinus communis L. seeds - Bin Han; D. Wayne Hughes; Glenn A. Galau; J. Derek Bewley; Allison R. Kermode (Planta, 1997)

Cysteine ligand vibrations are responsible for the complex resonance Raman spectrum of azurin - Colin R. Andrew; Jane Han; Tanneke den Blaauwen; Gertie van Pouderoyen; Erik Vijgenboom; Gerard W. Canters; Thomas M. Loehr; J. Sanders-Loehr (JBIC Journal of Biological Inorganic Chemistry, 1997)

Monitoring lead pollution near a storage battery recycling plant in Taiwan, Republic of China - C. -Y. Yeh; H. -Y. Chiou; R. -Y. Chen; K. -H. Yeh; W. -L. Jeng; B. -C. Han (Archives of Environmental Contamination and Toxicology, 1996)

Monitoring Lead Pollution Near a Storage Battery Recycling Plant in Taiwan, Republic of China - C.-Y. Yeh; H.-Y. Chiou; R.-Y. Chen; K.-H. Yeh; W.-L. Jeng, B.-C. Han (Archives of Environmental Contamination and Toxicology, 1996)

A neural network algorithm for the multiple traveling salesmen problem - E. Wacholder; J. Han; R. C. Mann (Biological Cybernetics, 1989)

2,3-diphosphoglycerate mutase: Its demonstration by electrophoresis and the detection of a genetic variant - Shi-Han Chen; Jeanne E. Anderson; Eloise R. Giblett (Biochemical Genetics, 1971)